Synergistic effect of zinc-chitosan co-modified rice husk biochar on nutrient retention and controlled release of fertilizer - Pinghui Wei; Yuyang Cong; Zuwang Shao; Yang Chen; Zhongjun Liu; Zepeng Cheng; Mingfeng Wang (Bioresource Technology, 2026)

Editorial Expression of Concern: Role of autophagy in early brain injury after subarachnoid hemorrhage in rats - Hongbo Zhao; Zhiyong Ji; Deji Tang; Cong Yan; Wenyang Zhao; Cheng Gao (Molecular Biology Reports, 2026)

Migration and transformation patterns of pesticides and their transformation products across the groundwater-surface water continuum - Jun Liu; Mengwen Liu; Guiyao Xiong; Yi Cheng; Cong Han; Hao Geng; Xuebing Wang; Si Wei; Nanyang Yu; Xiaobin Zhu; Jianfeng Wu; Xiankui Zeng; et al. (Water Research, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

S-CQD-enhanced cellulose-based multifunctional ratiometric fluorescent films: Improved fluorescent performance of FITC for freshwater shrimp freshness monitoring - Cong Chen; Boxin Zhang; Wenliang Wang; Jinbao Cheng; Bailiang Xue; Weikun Jiang; Lei Tian; Chengyuan Liang (Chemical Engineering Journal, 2026)

Deep metagenomic insights into ARG-MRG co-occurrence and potential bacterial hosts in landfill leachate-contaminated ecosystems - Shuyin Li; Haibing Cong; Yi Li; Cuicui Tao; Bipeng Yan; Haomiao Cheng; Wenxuan Chen; Tengyi Zhu (Journal of Environmental Chemical Engineering, 2026)

Unraveling the saltiness-enhancing effect of aroma compounds in soy sauce via integrated sensomics and molecular docking approaches - Peilin Yang; Qian Zhao; Cong Lyu; Donghong Liu; Xingqian Ye; Huan Cheng (Food Chemistry, 2026)

A graded MDA-equivalent dietary challenge disrupts intestinal homeostasis and compromises flesh quality in hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Tao Cheng; Cong Peng; Shiwei Xie; Shuyan Chi; Beiping Tan; Junming Deng (Food Bioscience, 2026)

Molecular bridging at the buried interface enables defect passivation and enhanced charge transport in efficient n-i-p perovskite solar cells - Jiahao Cheng; Limeng Zhao; Ke Liu; Yongxuan Zhou; Cong Geng; Wenjian Shen; Guijie Liang; Meihua Chen; Bin Li; Yong Peng; Jianlin Xu; Zaifang Li; et al. (Chemical Engineering Journal, 2026)

A high-performance triboelectric acoustic sensor enabled by synergistic structural and material optimization for intelligent voiceprint and laryngeal vibration recognition - Zhongxin Wang; Mingzhe Cai; Zekun Wang; Shuaining Cheng; Siyu Chen; Teng Wang; Ao Wang; Congcong Hao; Cong Zhai; Chenyang Xue (Chemical Engineering Journal, 2026)

Multi-objective optimization for multi-zone HVAC system via physics-integrated predictive control framework with CFD-assisted visualization - Fangli Hou; Jack C.P. Cheng; Cong Huang; Ang Li; Helen H.L. Kwok; Zhaoji Wu (Building and Environment, 2026)

PbrSLAH3b mediates nitrate-dependent regulation of pollen tube growth in pear - Guodong Chen; Peng Cao; Jia Gao; Weitao Xiao; Cong Jing; Rui Cheng; Huijun Jiao; Jizhong Wang; Juyou Wu (Plant Science, 2026)

New insight into the role of lipids in the formation and retention of key aroma compounds in micro-pressure stewed beef based on lipidomics and lipid-derived free radical analysis - Huan Liu; Yu Liu; Xinhe Zhang; Bo Xiao; Pi Li; Peng Gao; Jiangtao Xing; Weiting Wang; Pengfei Du; Jingxian Cong; Chengyu Zeng; Cheng Li; et al. (Food Research International, 2026)

Analysis of Electromagnetic Response Characteristics of Energized Subsea Cables in Complex Scenarios - Qi-feng Xiao; Cong Zhou; Min Feng; Cheng-hong Miao; Ju-zhi Deng; Shao-dong Zhang (Applied Geophysics, 2026)

Magnetic MnFe2O4 modified sludge biochar for peroxymonosulfate activation to enhance deep dewatering of excess sludge: Performance and synergistic mechanism - Jinyun Guan; Kai Cheng; Cong Zhang; Yihang Sun; Yichenyang Li; Chong Li; Jifeng Guo (Process Safety and Environmental Protection, 2026)

Exogenous calcium modulates oxalic acid metabolism via repression of LcAAE3 and mediates calcium accumulation in litchi pericarp and fruit pedicel - Dong-Cheng Li; Zhi-Qun Zhong; Teng-Kai Chen; Yi-Tong Liu; Yue-Han Sun; Hui-Cong Wang; Ren-Fang Zeng; Xu-Ming Huang (Journal of Plant Physiology, 2026)

Seismic reflection profiles reveal the Changjiangbu Fault and shallow structural features in the Ying-Yun Sag, northeastern Jianghan Basin - Cong Jin; Song Lin; Xiaohu Deng; Daicheng Peng; Fei Cheng (Journal of Applied Geophysics, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Quantum reinforcement learning for dynamic multi-objective energy management in community microgrids - Yan Gu; Huiru Yan; Qingle Wang; Cong Liu; Cheng Liu; Long Cheng (Energy and Buildings, 2026)

Validation of a Qualitative Detection Method for Influenza A Virus RNA Based on the RT-RPA-CRISPR/Cas13a System - Cong Peng; Cheng Zhang; Tong Jiang (Current Microbiology, 2026)

Eastward intracontinental reworking of the Qinling Orogen driven by far-field paleo-pacific slab tearing and rollback - Feng-Ran Cheng; Ren-Zhi Zhu; Peter Luffi; Min Liu; Jiang-Feng Qin; Shao-Cong Lai (Earth-Science Reviews, 2026)

Facile construction of a dual pH/redox-responsive nanopesticide for precise control of Fusarium graminearum with enhanced biosafety - Li Sun; Demei Xing; Zhen Li; Yanyan Gao; Yue Peng; Jiale Zhang; Yue Gao; Ruihan Gong; Cong Zhou; Jiagao Cheng (Chemical Engineering Journal, 2026)

Mechanistic insights into glufosinate-ammonium (GLA)-Induced brain injury revealed by LC-MS/MS-based metabolomics - Huan-le Ye; Xin-xin Zheng; Mian-mian Li; Zhi-qiang Zhang; Liu-xu Chen; Wen-jing Zhang; Ren Cheng-Han Fan; Guo-xin He; An-cong Xu (Chemico-Biological Interactions, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

A comparative analysis of CMIP5 and CMIP6 ensembles in attribution of global land extreme precipitation events - Qixuan Chen; Zeyu Zhang; Jinxin Zhu; Dagang Wang; Yiwen Mei; Cong Dong; Guanhui Cheng (Climatic Change, 2026)

3D gravity and magnetic joint inversion based on a double branch multi-channel CNN - Wan-cong Jiang; Yong-hui Zhao; Jin-yao Gao; Shuang-cheng Ge; Zhi-fei Xie (Applied Geophysics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Influence of ground pressure on grounding performance of deep-sea mining vehicle tracks - Junlin Zhao; Manhong Li; Hao Zheng; Yangrui Cheng; Zhou Li; Cong Ding; Andi Yu; Gen Li (Ocean Engineering, 2026)

Green immobilization of lipase based on a catechol-polyamine coating for efficient synthesis of octenyl succinic anhydride starch - Xiaolu Liu; Zhenyu Hu; Yao Li; Bozhi Tan; Jing Tian; Cong Wang; Sheng Cheng; Xu Fei (Food Chemistry, 2026)

Multifunctional interface engineering enables high efficiency of semi-transparent CsPbBr3 solar cells - Ankang Shu; Mingming Li; Jiawei Song; Zhengyang Li; Qian Wang; Shangwei Huang; Jiahao Cheng; Wenjian Shen; Cong Geng; Rui Chen; Guijie Liang; Jun Yao; et al. (Chemical Engineering Journal, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

Collaborative planning methodology for observation and data transmission missions of the lunar far side and polar landing regions - Xiaohan Mei; Wenkai Zheng; Yiqin Cong; Shengxin Sun; Cheng Wei (Advances in Space Research, 2026)

Divergent redistribution behavior of arsenic and antimony during schwertmannite transformation in presence of cysteine - Miaosha Cheng; Qi Huang; Xiaohu Jin; Qian Yao; Cong Fan; Xiaofei Li; Lijuan Zeng; Haiming Cai; Xueqin Tao; Guining Lu; Zhi Dang (Environmental Pollution, 2026)

Genetic mapping and identification of a major quantitative trait locus associated with the high fiber strength introgressed from Gossypium barbadense - Kai Wang; Haohong Tang; Cong Sun; Xiaohu Ma; Shen Ren; Jie Li; Xinyu Zhang; Shuaishuai Cheng; Xianpeng Xiong; Jie Sun (Plant Cell Reports, 2026)

Gas hydrate reservoir quality enhanced by framboidal pyrite formation - Qiang Song; Jiasheng Wang; Thomas J. Algeo; Can Chen; Zhou Wang; Muhui Zhang; Cong Cheng; Kunlong Geng (Frontiers in Marine Science, 2026)
Gas hydrate enrichment mechanisms and reservoir characteristics are crucial for understanding their resource potential and role in the global carbon cycle. Traditional models emphasize coarse-grained sediments as primary hosts for hydrates, but recent studies show significant accumulations also occur in fine-grained systems. However, the influence of authigenic minerals, particularly porous framboidal pyrite, on reservoir properties in such settings remains poorly understood. This study examines framboidal pyrite from three gas hydrate drillsites in the northern South China Sea: GMGS4-SC-W02B and GMGS4-SC-W03B in the Pearl River Mouth Basin, and GMGS2–16 in the Taixinan Basin. Integrated sedimentological, mineralogical, and petrophysical analyses, including scanning electron microscopy (SEM) and micro-computed tomography (micro-CT), show that framboidal pyrite aggregates exhibit substantial porosity (ranging from 8.1% to 80.2%) and well-connected pore networks that enhance sediment permeability and provide favorable storage space for gas hydrates. Key controlling factors include framboid size, microcrystal morphology, and size, all of which are influenced by geochemical conditions associated with anaerobic oxidation of methane (AOM). Additionally, pyrite microcrystals promote hydrate nucleation through their high specific surface area, defect-rich surfaces, and hydrophilic interactions, which enhance methane adsorption and facilitate heterogeneous crystallization. These findings demonstrate that framboidal pyrite actively facilitates hydrate storage and precipitation, rather than being a passive diagenetic product influenced solely by methane flux from hydrate dissociation, offering a refined geological framework for resource assessment and predictive exploration in fine-grained hydrate systems globally.

A constraint violation-based adaptive switching surrogate-assisted evolutionary algorithm for expensive constrained multiobjective optimization - Xu Cheng; Yongkuan Yang; Cong Zhu; Xiangsong Kong; Jianchang Liu (Swarm and Evolutionary Computation, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Slope and grain size control on channel-levee development in mixed turbidite-contourite systems - Long He; Tao Jiang; Man Tang; Dongmei Tian; Licheng Cao; Cong Cheng (Marine Geology, 2026)

Multi-metal/MOF-derived N-doped carbon electrocatalysts: Synergistic enhancement for practical oxygen reduction - Xuan Yang; Cong Li; Cheng Li; Jinrong Lu; Chenxin Wang; Hua Liu (Journal of Environmental Chemical Engineering, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Application of ENU-mediated efficient mutagenesis in breeding of the big belly seahorse (Hippocampus abdominalis) - Xiao-lei Su; Chun-yu Hou; Lin Shi; Shi-chang Zhang; Cheng-de Fan; Jie-zhou Wang; Yi-cong Ma; Wu-hong Lv; Cong Liu; Guo-dong Zheng; Kai Wang (Aquaculture, 2026)

Emerging contaminants disrupt the nitrogen cycle in coastal hydrological systems: Insights from synergistic effects of weakly-correlated emerging contaminants - Guiyao Xiong; Mengwen Liu; Xiaobin Zhu; Hao Geng; Cong Han; Yi Cheng; Yun Yang; Guangquan Chen; Xingyong Xu; Jianfeng Wu; Jinguo Wang; Nanyang Yu; et al. (Water Research, 2026)

Molecular mechanisms of ion hydration and gas–water diffusion joint controlled the CO2 hydrate growth - Hu Wenfeng; Sun Xiyue; Cheng Chuanxiao; Wu Xuehong; Zhang Xueling; Wang Fan; Zhu Shiquan; Qi Tian; Xiao Yanqiu; Chen Cong (Fuel, 2026)

Improvements in vibroseis source technology towards low frequencies - Ming-tao Nie; Zhou-hong Wei; Yong-fei Qi; Yang Liu; Yong-an Xu; Cheng-kuan Zhou; Sheng-kui Cong; Hai Ling; Gene-L. Wei (Applied Geophysics, 2026)

Reservoir property estimation of interbedded sandstone and shale layers using segmented 3D rock-physics templates - Jing Ba; Xi-Ya Ba; Hong-Jing Dong; Jun-Wei Cheng; Cong Luo; Zhi-Fang Yang; Meng-Qiang Pang; Wen-Hui Tan (Applied Geophysics, 2026)

Autumnicola aciditolerans sp. nov., a novel member of the genus Autumnicola isolated from tidal flat in Zhoushan - Yang Li; Dong-Yan He; Jia-Wei Gao; Ke Cao; Yun-Fei Cao; Xing-Cheng Wang; Lin Xu; Yan Bai; Can Chen; Cong Sun (Antonie van Leeuwenhoek, 2026)

An operational decision tree strategy optimizing the pairing of receptor model and classification approach in source apportionment of microplastics: Leveraging target source type and complexity - Cong Men; Jiayao Liu; Ke Xiong; Daniel Coulibaly; Nina Yang; Thi Kim Oanh Le; Loi Tan Huynh; The Anh Luu; Zhen Yang; Shikun Cheng; Zifu Li (Journal of Hazardous Materials, 2026)

Research on identification, functional characteristics, and applications of milk fat globule membrane proteins - Xiaoyu Ma; Yu Wan; Xingyu Bao; Jian He; Sufang Duan; Gang Feng; Haixia Wu; Shuzhen Cheng; Cong Wang (International Dairy Journal, 2026)

Has rising bottom water temperature since the Last Glacial Maximum caused gas hydrate dissociation? - Cong Cheng; Tao Jiang; Zenggui Kuang; Zigui Chen; Jinfeng Ren; Hongfei Lai; Licheng Cao; Qianru Wang; Yipan Hu; Lin Song; Chen Liang; Xu Zhao; et al. (Global and Planetary Change, 2026)

Sheep skin collagen peptide enhances Treg immunosuppressive function through modulation of Foxp3-Rora/ Il23r axis - Jianyang Cong; Qi Yang; Xinran Liu; Zhihui Chang; Peiting Lv; Heyuan Gao; Shuzhen Cheng; Ming Du (Food Bioscience, 2026)

Room-temperature fabricated boron nitride ceramics with superior thermal conductivity - Jin Cheng; Li Li; Naichao Chen; Hongye Wang; Xinwei Xu; Zhan Zeng; Jiufeng Dong; Liang Sun; Yani Lu; Cong Liu; Fei Jin; Hong Wang (Chemical Engineering Journal, 2026)

Function and mechanisms of polyethylene glycol-modified sodium acrylate-acrylamide hydrogel for microalgal biomass enrichment and purification - Cong-Cong Tang; Qiao Zhong; Yi Liu; Yong-Qi Cheng; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Phytoremediation of antibiotics and antibiotic resistance genes by Hydrilla verticillata: Synergistic removal and mechanistic insights - Huimin Wei; Lu Zhang; Yujie Mao; Yiting Cheng; Cong Wang; Zhi Wang (Bioresource Technology, 2026)

Straw-decomposing inoculants strengthen the mitigation effect of straw on N2O emissions via synergistically inhibiting the abundance and activity of AOB in a wheat field - Cheng Ji; Pizhen Yang; Jing Wang; Jieru Liu; Jie Zhou; Cong Xu; Jie Yuan; Dong Liang; Naijuan Hu; Yunwang Ning; Yongchun Zhang; Jidong Wang (Plant and Soil, 2026)

Ni and Mo enrichment mechanisms in framboidal pyrite during methane-release events (Baiyun Sag, South China Sea) - Qiang Song; Jiasheng Wang; Thomas J. Algeo; Liyuan Xu; Can Chen; Zhou Wang; Cong Cheng; Kunlong Geng; Qing Li (Frontiers in Marine Science, 2026)
Framboidal pyrite, a common form of authigenic pyrite in marine sediments, forms through the co-precipitation of equant, equidimensional microcrystals that can effectively sequester trace elements. Nevertheless, the relationships among key attributes of framboids (i.e., framboid size, microcrystal dimensions, and number of microcrystals) and the detailed mechanisms of trace−element enrichment within framboids are not yet well understood. To address this gap, we present a dataset encompassing framboid key attributes, sulfur isotopes, and trace−element (Ni, Mo) concentrations from two gas−hydrate−bearing drillsites (GMGS4−SC−W02B and GMGS4−SC−W03B) in the Shenhu area, Pearl River Mouth Basin, South China Sea. In this methane−seep−influenced setting, framboid size is primarily controlled by microcrystal diameter and secondarily by microcrystal abundance. Nickel enrichment in framboidal pyrite follows a two−stage mechanism. Initially, Ni is taken up into FeS precursors before being incorporated into pyrite via isomorphous substitution on {111} microcrystal surfaces during framboid growth. This results in a strong positive correlation with microcrystal size (R² = 0.73, p < 0.001) rather than with their number (R 2 = 0.18, p = 0.02). In contrast, Mo content shows positive correlations with both framboid size and microcrystal abundance (R² = 0.66, p < 0.01 and R² = 0.42, p = 0.01, respectively), consistent with its incorporation as nano−inclusions or nanoparticles within the pyrite lattice. The enrichment of both elements initiates from the strong adsorption capacity of iron monosulfide precursors. In methane release environments, enhanced anaerobic oxidation of methane facilitates the conversion of molybdate to particle-reactive thiomolybdates, which are effectively captured by growing pyrite framboids. Nickel, on the other hand, benefits from the increase in microcrystalline surface area during growth, where it replaces exposed Fe 2+ through isomorphic substitution, leading to enrichment on microcrystal surfaces. This study advances the mechanistic understanding of trace−element incorporation in framboidal pyrite, and these findings strengthen the reliability of nickel and molybdenum as robust proxies for reconstructing paleoenvironmental conditions and paleo-methane release activity.

Sulfonic acid functionalized cupric sulfide electrodes with gel network synergy enable efficient and selective copper recovery via hybrid capacitive deionization - Yingjun Gao; Yinyan Guan; Jiyan Liang; Yanjie Zhang; Shengnan Chen; Cong Geng; Weichun Gao; Xueyong Tian; Dehong Cheng (Process Safety and Environmental Protection, 2026)

Efficiency of photoelectrocatalytic oxidation integrated with moving bed biofilm reactor for advanced treatment of dyeing wastewater - Jiapeng Liu; Fengjuan Xiao; Qianying Zong; Yifan Liu; Xin Cheng; Zhixin Wang; Xiaohong Yang; Cong Liu (Journal of Water Process Engineering, 2026)

Novel mechanisms of cadmium detoxification mediated by selenium nanoparticles in selenium hyperaccumulator plants: Discovery of HSP90-1 as a pivotal potential regulatory hub - Wei Yang; Shang Gao; Qiangwen Chen; Weiwei Zhang; Min Xie; Xin Cong; Shuiyuan Cheng; Feng Xu (Journal of Cleaner Production, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

Multifunctional polymeric mixed conductors via benzochalcogenodiazole heteroatom engineering enables high-performance and ultra-stable aqueous electrochemical devices - Chaoyue Chen; Junxin Chen; Donghao Li; Miao Xie; Guohong Hu; Runxia Wang; Jiaqi He; Shengyu Cong; Jiayao Duan; Wei Huang; Zhengke Li; Yuhua Cheng; et al. (Chemical Engineering Journal, 2026)

Quantifying heavy metal(loid)s sources in subtropical soils and assessing key determinants of their bioavailability: insights from the Yangtze River Delta, China - Minqi Shi; Cheng Wang; Jianhua Wang; Cong Zhong; Yanping Zhao (Plant and Soil, 2026)

AMF modulation of sweet potato plant performance and rhizosphere microecology depends on soil potassium availability: shared and differential strategies - Jie Yuan; Wenna Zhao; Xiaoqing Wu; Cheng Ji; Lei Wang; Cong Xu; Dong Liang; Bing Feng; Guopeng Zhu; Fei Chen; Jidong Wang; Yongchun Zhang (Plant and Soil, 2026)

Divergent occupational heat stress strategies required for Northern and Southern China under climate change - Zhengyuan Liu; Wei Liu; Shuo Wang; Xiuquan Wang; Jinxin Zhu; Dagang Wang; Cong Dong; Guanhui Cheng; Yiwen Mei; Xiaoxing Qi (International Journal of Biometeorology, 2026)

Biodiversity gains importance in sustaining ecosystem multifunctionality when beyond aridity thresholds in temperate grasslands - Yu Yang; Changchao Zhang; Mingxing Tian; Binwei Ci; Cong Liu; Yunxiang Cheng; Pujin Zhang; Hongtao Luo; Liqing Zhao; Yonghui Wang; Wenhong Ma (Agriculture, Ecosystems & Environment, 2026)

Recent advances in composite caisson–pile foundation - Zhihe Cheng; Shengyi Cong; Zhiqiang Cheng (Marine Georesources & Geotechnology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Luminescence chronology of IODP Site U1431A since the Late Pleistocene in the South China Sea - Cong Cheng; Tao Jiang; Yipan Hu; Qianru Wang (Quaternary Science Reviews, 2025)

Structure-based molecular design of fungicidal β-ketonitrile derivatives with biphenyl moiety as novel succinate dehydrogenase inhibitors - Cong Zhou; Ziye Cao; Li Sun; Na Zhai; Liangliang Cheng; Zheyi Feng; Zhong Li; Xuhong Qian; Jiagao Cheng (Pesticide Biochemistry and Physiology, 2025)

Monsoonal intensity dominated the Eocene evolution of paleovegetation and paleoclimate in northern South China Sea - Jinhua Zeng; Tao Jiang; Keqiang Wu; Desheng Hu; Yong Man; Licheng Cao; Cong Cheng; Zigui Chen; Kun Wang; Nan Bai; Meiling Feng; Ziyi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

WSSV regulates malate-aspartate shuttle during infection - Yen Siong Ng; Fang-Jyun Guo; Kuan-Lun Huang; Cong-Yan Chen; Shu-Wen Cheng; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Promoting nitrogen removal in low C/N wastewater treatment by S0 packed-bed process: Post polishing or via disproportionating sulfidogenesis enhancement - Cong Fang; Guijiao Zhang; Wenwei Liao; Ran Zeng; Na Zhang; Bin Gao; Jiamin Xu; Chengyan Liu; Aijie Wang; Hao-Yi Cheng (Chemical Engineering Journal, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

Understanding the formation of starch structure during grain development in two wheat cultivars with different filling rate - Faji Li; Cong Zhao; Dengan Xu; Dungong Cheng; Aifeng Liu; Shengnan Zhai; Jun Guo; Yan Zi; Xinyou Cao; Cheng Liu; Jianmin Song; Haosheng Li; et al. (Carbohydrate Polymers, 2025)

Role of oxidative stress in intervertebral disc degeneration: mechanisms, pathogenesis, and therapeutic strategies - Cong Zhang; Cheng-ming Li; Qing Jiang (Molecular Biology Reports, 2025)

Glass bead-supported Eu3+/Bi2WO6 packed-bed reactor for efficient photocatalytic removal of tetracycline - Huadong Liu; Jingliang Cheng; Xiaoyu Sun; Zhonghao Zhao; Cong Zhang (Journal of Water Process Engineering, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Development of a distributed monitoring method for soil suction based on optic-fiber sensing technique - Wen Mu; Chao-Sheng Tang; Qing Cheng; Jin-Jian Xu; Hui-Cong Hu; Qi-You Zhou (Engineering Geology, 2025)

Sodium dodecylbenzene sulfonate (SDBS) assisted interfacial polymerization on a macro-porous nanofibrous support layer to prepare high-performance forward osmosis membranes - Cong Ma; Mengyuan Su; Zhaoyang Cheng; Meng Zhang; Yishan Chen; Liang Wang (Desalination, 2025)

Temperature-triggered self-lubricating behaviour via bioinspired multifunctional rigid polymer for adaptive friction control - Zhicheng Chen; Hui Shen; Cheng Zhou; Cong Du; Yiheng Song; Shiwen Yang; Xianze Yin (Chemical Engineering Journal, 2025)

Occupancy-driven HVAC control optimization via LSTM and deep reinforcement learning for enhanced indoor air quality, thermal comfort and energy efficiency - Fangli Hou; Jack C.P. Cheng; Jun Ma; Helen H.L. Kwok; Cong Huang; Zhaoji Wu (Building and Environment, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

The nitrate dynamics affected by land use and saltwater intrusion in the coastal hydrologic interaction systems - Hao Geng; Guiyao Xiong; Mengwen Liu; Cong Han; Yi Cheng; Jichun Wu; Shaohua Cao; Xiaobin Zhu (Journal of Hazardous Materials, 2025)

Effect of pulsation frequencies on the fracture characteristics of CO2 foam fractured coal: An experimental study - Yangfeng Zheng; Cheng Zhai; Aikun Chen; Hexiang Xu; Xinyu Zhu; Shuxun Sang; Meng Wang; Shiqi Liu; Xu Yu; Jizhao Xu; Yong Sun; Yuzhou Cong; et al. (Gas Science and Engineering, 2025)

Bifunctional CMCS bioswitch: A stimuli-responsive platform neutralizing lambda-cyhalothrin resistance and mitigating ecological risk - Zeyu Wang; Mingxia Liu; Zehua Cheng; Zehao Li; Kexin Zhang; Jing Li; Yifan Zhang; Zihao Fan; Lianrui Cao; Lijiang Chen; Cong Li (Chemical Engineering Journal, 2025)

High-sensitivity and self-powered flexible pressure sensor based on multi-scale structured piezoelectric composite - Hu Zhao; Xiaoming Chen; Chaojie Xin; Fengwan Zhao; Siyi Cheng; Mengyong Lei; Cong Wang; Jingyao Zhang; Xiaoliang Chen; Hongmiao Tian; Jie Zhang; Jinyou Shao (Chemical Engineering Journal, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

Feedback inhibition derived from hydrogen sulfide in microbial sulfidogenic process via elemental sulfur disproportionation - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xuchen Ba; Wenyan Mao; Wenke He; Cong Fang; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Late Quaternary oceanographic controls on sediment distribution and transportation in the Southeast Indian Ocean; insights from IODP Site U1516 - Maqsood Ur Rahman; Tao Jiang; Muhammad Sarim; Qianru Wang; Cong Cheng (Sedimentary Geology, 2025)

Paleoceanography and marine ecosystem over 250 ky offshore Southwest Western Australia; Insight from nannofossil assemblages - Maqsood Ur Rahman; Tao Jiang; Muhammad Sarim; Qianru Wang; Muhammad Hanif; Cong Cheng (Marine Micropaleontology, 2025)

Machine learning-based detection of dynamic changes in mangrove forest, Beilun Estuary - Chuqi Long; Zhijun Dai; Xuefei Mei; Xixing Liang; Xuewei Zhang; Yangyang Xi; Riming Wang; Nguyen An Binh; Cong Mai Van; Jinping Cheng (Ocean & Coastal Management, 2025)

Timing and structure of the short-lived Dansgaard-Oeschger 6 event in the Asian monsoon system - Qiyue Li; Jingjing Lu; Chenyang Zhang; Guhan Liu; Bin Zhao; Jiaqi Cong; Yue Yang; Kan Zhao; Jinguo Dong; Hai Cheng; Yujie Han; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

An in-situ gold growth self-catalytic signal amplification system enhanced hollow gold immunochromatography for ultrasensitive detection of p24 antigen in HIV infection - Chuanjiang Ran; Qingjie Zhang; Zhenglin Long; Yuhao Li; Xinyue He; Shengzhou Li; Chen Chen; Cong Cheng; Ying Xu; Wenli Zhang; Wei Guo; Yan Shen (Chemical Engineering Journal, 2025)

Graph-based spatial–temporal prediction and feature interaction analysis of CO 2 and occupant in large indoor space - Cong Huang; Helen H.L. Kwok; Kwok Ho Poon; Zhaoji Wu; Fangli Hou; Jun Ma; Jack C.P. Cheng (Building and Environment, 2025)

A complete and continuous core record of deep-water mass transport deposits - Cong Cheng; Tao Jiang; Zenggui Kuang; Jinfeng Ren; Zigui Chen; Xu Zhao; Maqsood Ur Rahman; Fulong Ning (Frontiers in Marine Science, 2025)
Mass transport deposits are a fundamental component of deep-water sedimentary systems and play a crucial role in the transportation of sediments from continental slopes to deep-sea basins. However, there exists a significant gap in our understanding of their internal vertical structure, core facies characteristics, and associated sedimentary processes. This study employs comprehensive and continuous core data, logging-while-drilling data, and high-resolution 3D seismic data obtained from the Qiongdongnan Basin in the northern South China Sea to meticulously delineate the core facies of deep-water sedimentary systems within the investigated area. Among these findings, eleven core facies types have been summarized and categorized across all identified sedimentary systems. These include mass transport deposits, turbidity currents, bottom currents, as well as hemipelagic and pelagic deposits. Mass transport deposits display a range of deformation characteristics within their cores, including slumps and debris flows. Their internal structure encompasses various sedimentation processes that involve not only turbidity currents but also hemipelagic and pelagic deposits. This study further explores the issue of phase division in mass transport deposits across various dataset scales, including core, log, and seismic data. It proposes new insights into sedimentary processes and patterns for mass transport deposits in deep-water environments while examining their dynamic interactions with gas hydrates. Additionally, this study summarizes the overall framework of deep-water sedimentary systems present in the Qiongdongnan Basin. The aim is to provide geological insights that will inform future studies on mass transport deposits.

A spatiotemporal mixed-enhanced generative adversarial network for radar-based precipitation nowcasting - Long He; Kun Zheng; Huihua Ruan; Shuo Yang; Jinbiao Zhang; Cong Luo; Siyu Tang; Yunlei Yi; Yugang Tian; Jianmei Cheng (Computers & Geosciences, 2025)

Hierarchical all-carbon nanozyme architectures for enhanced intelligent rutin detection - Cong Cheng; Mengxue Li; Chenyu Shi; Shiyu Hu; Min Chen; Yongbing Cheng; Qinyi Cao; Xiaoli Wang; Xiangya Kong; Zihao He; Guiping Liao; Zhaohong Su (Chemical Engineering Journal, 2025)

Translocation coefficients of heavy metals in the soil-rice system and their environmental implication - Cheng Wang; Minqi Shi; Jianhua Wang; Cong Zhong; Yanping Zhao (Plant and Soil, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Multi-Objective Optimization Based on Response Surface Methodology and Multi-Objective Particle Swarm Optimization for Pipeline Selection of Replenishment Oiler - Yujin Cong; Cheng Meng; Ming Yang; Yong Liu; Ping Yi; Tie Li; Shuai Huang (Journal of Marine Science and Engineering, 2025)
Ship pipeline selection, as a crucial component of ship pipeline design, is often a time-consuming process due to its high complexity. In this study, the response surface methodology combined with the multi-objective particle swarm optimization algorithm was used to optimize the fuel pipeline resistance and its space volume, aiming to select the optimal design scheme for an X-type replenishment oiler. Firstly, a one-dimensional pipeline system simulation model of a replenishment oiler was established based on the Flowmaster software (version 4.2_0 2020), and the fueling process was simulated. The simulation results were validated against the experimental results, and good agreements were obtained. Then, the response surface methodology was employed to establish regression models for the pipeline resistance, pipeline space volume, and imbalance degree of branch flows. Finally, multi-objective particle swarm optimization was used to optimize the target and select the optimal virtual solution from the Pareto front. Constrained by the international application standard, the optimal real solution was determined. Compared with the original scheme, the optimized scheme reduced the resistance by 3.57% for the #1 pipeline system and by 3.51% for the #2 pipeline system, respectively, and the space volume of the pipeline system was reduced by 5.72% while ensuring the flow balance.

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

Optimization of hydraulic retention time in continuous orange peel crude enzyme - mediated dark fermentation for sustainable biohydrogen production from synthetic swine wastewater - Siran Feng; Wenshan Guo; Shicheng Zhang; Gang Luo; Hau Thi Nguyen; Nguyen Cong Nguyen; Dongle Cheng; Yuanyao Ye; Huu Hao Ngo (Journal of Water Process Engineering, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Agile and creative: A sustainability-oriented generative framework for residential site layout design - Zhaoji Wu; Wenli Liu; Jack C.P. Cheng; Zhe Wang; Helen H.L. Kwok; Cong Huang; Fangli Hou (Energy and Buildings, 2025)

Geochemical characteristics of metal(loid)s in forest soil profiles affected by Pb-Zn ore mining - Cheng Wang; Minqi Shi; Jianhua Wang; Cong Zhong (Journal of Cleaner Production, 2025)

Real-time optimization for WEEE recycling routing problem with multiple service types - Yanfang Ma; Lina Liu; Siyu Huang; Cong Cheng; Zongmin Li (Journal of Cleaner Production, 2025)

Adaptive Discrepancy Masked Distillation for remote sensing object detection - Cong Li; Gong Cheng; Junwei Han (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Genome-wide identification of MYB gene family and exploration of selenium metabolism-related candidates in paper mulberry (Broussonetia papyrifera) - Changye Zhu; Qiangwen Chen; Longfei Guo; Shiming Deng; Weiwei Zhang; Shuiyuan Cheng; Xin Cong; Feng Xu (Plant Cell Reports, 2025)

Autonomous collaborative observation method for time-sensitive moving target tracking by satellite swarms - Yiqin Cong; Xiaohan Mei; Shengxin Sun; Tianxi Liu; Gongshun Guan; Cheng Wei (Advances in Space Research, 2025)

Regional abnormalities of white and gray matter in youths with conduct problems - Man Dong; Xiaodong Cheng; Yage Li; Shanling Ji; Hao Yu; Liangliang Ping; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

Facies-Controlled Sedimentary Distribution and Hydrocarbon Control of Lower Cretaceous Source Rocks in the Northern Persian Gulf - Yaning Wang; Wei Huang; Tao Cheng; Xuan Chen; Qinqin Cong; Jianhao Liang (Journal of Marine Science and Engineering, 2025)
The two-phase source rocks deposited during the Lower Cretaceous in the Persian Gulf Basin play a pivotal role in the regional hydrocarbon system. However, previous studies have lacked a macroscopic perspective constrained by the Tethyan Ocean context, which has limited a deeper understanding of their developmental patterns and hydrocarbon control mechanisms. To address this issue, this study aims to clarify the spatiotemporal evolution of the two-phase source rocks and their hydrocarbon control effects, with a particular emphasis on the critical impact of terrestrial input on the quality improvement of source rocks. Unlike previous studies that relied on a single research method, this study employed a comprehensive approach, including time series analysis, sequence stratigraphy, lithofacies, well logging, well correlation, seismic data, and geochemical analysis, to systematically compare and analyze the depositional periods, distribution, and characteristics of the two-phase source rocks under different sedimentary facies in the region. The goal was to reveal the intrinsic relationship between the Neo-Tethyan Ocean context and regional sedimentary responses. The results indicate the following: (1) the late Tithonian–Berriasian and Aptian–Albian source rocks in the Northern Persian Gulf were deposited during periods of extensive marine transgression, closely aligning with the global Weissert and OAE1d anoxic events, reflecting the profound impact of global environmental changes on regional sedimentary processes; (2) in the early stages of the Neo-Tethyan Ocean, controlled by residual topography, the Late Tithonian–Berriasian source rocks exhibited a shelf–intrashelf basin facies association, with the intrashelf basin showing higher TOC, lower HI, and higher Ro values compared to the deep shelf facies, indicating more favorable conditions for organic matter enrichment; (3) with the opening and deepening of the Neo-Tethyan Ocean, the Aptian–Albian source rocks at the end of the Lower Cretaceous transitioned to a shelf–basin facies association, with the basin facies showing superior organic matter characteristics compared to the shelf facies; (4) the organic matter content, type, and thermal maturity of the two-phase source rocks are primarily controlled by sedimentary facies and terrestrial input, with the Aptian–Albian source rocks in areas with terrestrial input showing significantly better quality than those without, confirming the decisive role of terrestrial input in improving source rock quality. In summary, this study not only reveals the differences in the depositional environments and hydrocarbon control mechanisms of the two-phase source rocks, but also highlights the core role of terrestrial input in enhancing source rock quality. The findings provide a basis for facies selection in deep natural gas exploration in the Zagros Belt and shale oil exploration in the western Rub’ al-Khali Basin, offering systematic theoretical guidance and practical insights for hydrocarbon exploration in the Persian Gulf and broader tectonic domains.

Advanced solar photo-Fenton-like process with directly growing nano-heterojunctions on graphite fiber felt for phenolic wastewater treatment: Synergistically expand the pH activity range and facilitate the Fe(III)/Fe(II) cycle - Qianying Zong; Xiaofei Niu; Xin Cheng; Yifan Liu; Cong Liu; Tingyue Shi; Jiapeng Liu; Xiaohong Yang; Wentao Wang; Zikuan Guo; Fengjuan Xiao (Chemosphere, 2025)

Hydrochemical processes and water balance trends based on stable isotopes of typical alpine lakes in the Qinghai-Tibet Plateau - Changchang Fu; Xiangquan Li; Xu Cheng; Cong Liu; Zhanxue Bai; Jinqiu Li (Journal of Geochemical Exploration, 2025)

Dependency of HRT on sulfidogenesis rate in S0 disproportionation pack-bed reactor - Cong Fang; Guijiao Zhang; Aijie Wang; Hao-Yi Cheng (Journal of Water Process Engineering, 2025)

Origin and evolution of slope-confined canyons and their relationship with gas hydrate accumulation in the northwestern Qiongdongnan Basin, South China Sea - Zigui Chen; Tao Jiang; Wenzhao Sun; Yue Chen; Cong Cheng; Ru Yin (Geomorphology, 2025)

Dynamics of microbial communities and organic carbon pools in karst wetland soils - Yutian Xiao; Congyu Cheng; Aoqi Cheng; Weihua Kang; Taiming Shen; Qingrong Yang; Cong Peng; Longjiang Yu; Wei Li (CATENA, 2025)

Stakeholder perspectives on ecosystem services in agricultural landscapes: A case study in the North China Plain - Jiali Cheng; Andries Richter; Wen-Feng Cong; Zhan Xu; Zhengyuan Liang; Chaochun Zhang; Fusuo Zhang; Wopke van der Werf; Jeroen C.J. Groot (Agricultural Systems, 2025)

Characteristics, source analysis, and risk assessment of organochlorine pesticide contamination in nearshore surface sediments of a tropical tourist island - Hongbing Wang; Lin Zhang; Feng Yang; Li Yan; Cong Lin; Cheng Shen (Frontiers in Marine Science, 2025)
Surface sediment samples were collected from the surrounding waters of the two largest tourist islands in Sanya, China, to compare and evaluate the sources, distribution, and ecological risks of 21 organochlorine pesticides (OCPs). The total concentration of OCPs ranged from 1.35 to 5.0 ng/g. Among the OCPs, ΣDDTs accounted for the largest proportion, followed by ΣHCHs. The concentrations of HCHs and DDTs from the west side of West Island were significantly higher than those from the east side, and fine-grained sediments exhibited a stronger adsorption effect on OCPs. Source analysis indicated that the area experienced new inputs of HCH pollutants, while historical residues of HCHs remained high. Residual OCPs are still widely present in the environment, transported mainly by river runoff, with a smaller portion originating from atmospheric deposition and ship paints. Ecological risk assessment results showed that factors occasionally causing adverse biological effects include Heptachlor epoxide, 4,4'-DDE, ΣDDT, Dieldrin, Endrin, and γ-HCH, while other factors rarely caused negative biological effects. Potential ecological effect evaluations indicated that stations SY03, SY04, SY06, and SY09 were classified as having moderate ecological effect levels, while other stations were classified as having no ecological effects. Strengthened investigation, monitoring, and control of pollutant sources in ecologically impacted areas are necessary. This study fills a data gap for the region and provides an academic foundation for environmental protection and the sustainable development of tourism resources.

New quantified climate reconstruction in southern China suggests a potential influence of winter cloud cover across East Asia during the Holocene - Xiao Zhang; Cong Chen; Kexin Wang; Meihuan Li; Yuanfu Yue; Jun Cheng; Mengna Liao; Kai Li; Lina Liu; Zhanghua Wang; Rachid Cheddadi; Qiuchi Wan; et al. (Science of The Total Environment, 2025)

New insights into the neurophysiological effects of heat stress on the Chinese mitten crab (Eriocheir sinensis) - Cong Zhang; Dunqian Deng; Yi Wu; Lexue Song; Jiayin Geng; Huixia Feng; Su Jiang; Kai Zhang; Yongxu Cheng; Shaowu Yin (Journal of Thermal Biology, 2025)

Insight into the anti-T2DM effect and mechanism of apricot polysaccharide through the combination of 16S rRNA sequencing and non-target metabolomics - Andi Suo; Gongjian Fan; Caie Wu; Tingting Li; Xiaojing Li; Dandan Zhou; Kaiping Cong; Xin Cheng (Food Bioscience, 2025)

Mercury methylation and bioaccumulation in purple paddy soil systems with different acid-base properties - Xinyi Ke; Jieqin Li; Anquan Xu; Juan Wang; Cong Yao; Yongmin Wang; Cheng Zhang; Dingyong Wang (Environmental Research, 2025)

Effects of rumen metabolite butyric acid on bovine skeletal muscle satellite cells proliferation, apoptosis and transcriptional states during myogenic differentiation - Xiao-Wei Wang; Yan-Ling Ding; Cheng-Long Li; Qing Ma; Yuan-Gang Shi; George E Liu; Cong-Jun Li; Xiao-Long Kang (Domestic Animal Endocrinology, 2025)

Hyaluronanized gold nanoparticles functionalized with CTX-II antibody for early diagnosis and treatment of knee osteoarthritis - Cheng Chen; Cong Tang; Kaiquan Chen; Muhai Deng; Xiangling Pu; Tao Hu; Zhiyu Chen; Ling Zhong; Yunsheng Jiang; Yang Huang (Chemical Engineering Journal, 2025)

Regionalized ensemble estimation of wave periods for assessing wave energy resources across Canada. Part II: Wave-period and wave-energy analyses - Cong Dong; Gordon Huang; Guanhui Cheng; Yanpeng Cai; Jinxin Zhu; Shan Zhao (Ocean & Coastal Management, 2024)

Regionalized ensemble estimation of wave periods for assessing wave energy resources across Canada. Part I: Improved wave-period modelling methodology - Cong Dong; Gordon Huang; Guanhui Cheng; Yanpeng Cai; Jinxin Zhu; Shan Zhao (Ocean & Coastal Management, 2024)

Precipitation-induced biomass enhancement and differential allocation in Inner Mongolia's herbaceous and shrub communities - Xiangyun Li; Ya Hu; Zhaobin Song; Ping Cong; Huan Cheng; Xuebo Zheng; Wenjing Song; Ping Yue; Shaokun Wang; Xiaoan Zuo (Science of The Total Environment, 2024)

Research on layout optimization for propellers of a submarine operation vehicle - Long Xiao; Yu Dai; Cong Xue; Wei-Bin Ma; Cheng-Long Liu (Ocean Engineering, 2024)

Relationship between root characteristics and saturated hydraulic conductivity in a grassed clayey soil - Ling-Xin Cui; Qing Cheng; Pui San So; Chao-Sheng Tang; Ben-Gang Tian; Cong-Ying Li (Journal of Hydrology, 2024)

Biogeochemical process governing cadmium availability in sediments of typical coastal wetlands driven by drying-wetting alternation - Cheng-Cheng Jiang; Guang-Hui Yu; Xiao-Jie Zhou; Fu-Sheng Sun; Cong-Qiang Liu (Journal of Hazardous Materials, 2024)

Immobilizing lead in aqueous solution and loess soil using microbially induced carbonate/phosphate precipitation (MICP/MIPP) under harsh pH environments - Zhong-Fei Xue; Wen-Chieh Cheng; Lin Wang; Yi-Xin Xie; Peng Qin; Cong Shi (Journal of Hazardous Materials, 2024)

Efficient preparation of diglycerides from rapeseed oil sediment using phospholipase C in a solvent-free phospholipid hydrolysis system - Yanxia Cong; Yiwei Liu; Manyu Yuan; Ying Cheng; Jiangtao Feng; Jiangke Yang; Weinong Zhang (Food Bioscience, 2024)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

The CDK4/6 Inhibitor Palbociclib Induces Cell Senescence of High-grade Serous Ovarian Cancer Through Acetylation of p53 - Cong Ye; Yan Cheng; Xiaohong Qian; Bo Zhong; Jinchun Ma; Hongling Guo (Biochemical Genetics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Promoted production of Fe(IV)/Fe(V) intermediates in the calcium peroxide/ferrate(VI) process for low-damage removal of algal contaminants and membrane fouling control - Jinchuan Lian; Shuai Shi; Jiaxin Bao; Xiangchen Cong; Jin Wang; Heng Liang; Xiaoxiang Cheng (Journal of Hazardous Materials, 2024)

Thermal decomposition behaviors of adamantane and 1-methyladamantane in oxygen atmosphere: ReaxFF molecular dynamics simulation - Liang Song; Tian-Cheng Zhang; Yong Zhang; Bo-Cong Chen; Jing Ye; Fang-Chao Hou; Jing Sun; Su-Qin Zhou (Fuel, 2024)

Chemical regulation of lignin spatial conformation for a multifunctional soft material with a novel energy dissipation mechanism - Yingying Su; Xiao Han; Guanda Che; Jinghui Zhou; Yao Li; Sheng Cheng; Cong Wang; Xu Fei (Chemical Engineering Journal, 2024)

A microfluidic analyzer based on liquid waveguide capillary cells for the high-sensitivity determination of phosphate in seawater and its applications - Jincheng Zhao; Zeming Yang; Dejing Tang; Min Qin; Wen Zhou; Cong Liu; Zhantang Xu; Yuanyue Cheng; Xianqing Zhang; Cai Li (Analytica Chimica Acta, 2024)

Molecular imprinting electrochemical sensor based on hollow spherical PProDOT-2CH2OH and chitosan-derived carbon materials for highly sensitive detection of chloramphenicol - Qian Cheng; Cong Xue; Tursun Abdiryim; Ruxangul Jamal (Journal of Hazardous Materials, 2024)

Transcriptional RNA sequencing reveals the molecular mechanism of dielectric barrier discharge cold plasma against postharvest pathogen Alternaria alternata - Tingting Li; Xiaodong Chen; Jinfeng Cheng; Zhicheng Yan; Caie Wu; Dandan Zhou; Gongjian Fan; Xiaojing Li; Kaiping Cong; Xu Li (Food Bioscience, 2024)

Unlocking soil revival: the role of sulfate-reducing bacteria in mitigating heavy metal contamination - Cheng Hu; Zhendong Yang; Yijing Chen; Jiayi Tang; Li Zeng; Cong peng; Liudong Chen; Jing Wang (Environmental Geochemistry and Health, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Unveiling the dynamics of co-created camping experiences: Influence of co-production on family cohesion and resilience via place identity - You-De Dai; Shih-Shuo Yeh; Minh Cong Nguyen; Chien-Wen Hung; Tzung-Cheng Huan (Journal of Outdoor Recreation and Tourism, 2024)

Multilevel regulation of Li+-solvent interaction for fluorophosphate-based nonflammable electrolyte enabling lithium-ion batteries with long calendar life - Mengchuang Liu; Ziqi Zeng; Hui Yan; Qiang Wu; Yuanke Wu; Wei Liu; Sheng Lei; Cong Liao; Xinping Ai; Shijie Cheng; Jia Xie (Chemical Engineering Journal, 2024)

Comprehensive improvement of AB2 hydrogen storage alloy: Substitution of rare earth elements for different A-side alloys - Wenfeng Qiao; Wanqiang Liu; Dongming Yin; Nan Ding; Shaolei Zhao; HaiXiang Xiu; Cong Liu; Ying Wang; Miao He; Chunli Wang; Limin Wang; Yong Cheng (Chemical Engineering Journal, 2024)

Application of pyrite trace-metal and S and Ni isotope signatures to distinguish sulfate- versus iron-driven anaerobic oxidation of methane - Can Chen; Jiasheng Wang; Thomas J. Algeo; Jian-Ming Zhu; Simon W. Poulton; Zhou Wang; Cong Cheng; Qiang Song (Chemical Geology, 2024)

Analysis of Fracture Network Formation Mechanisms and Main Controlling Factors of Methane Explosion Fracturing in Deep Shale Reservoir - Yu Wang; Cheng Zhai; Ting Liu; Xu Yu; Jizhao Xu; Yong Sun; Yuzhou Cong; Wei Tang; Yangfeng Zheng; Ning Luo (Rock Mechanics and Rock Engineering, 2024)

Distribution and ecological risk assessment of antibiotics in different freshwater aquaculture ponds in a typical agricultural plain, China - Lu Zhang; Huimin Wei; Cong Wang; Yiting Cheng; Yong Li; Zhi Wang (Chemosphere, 2024)

Integrating experiments with modeling to understand key bacterial taxa dynamics after episodic mixing of a stratified water column - Hainan Wu; Yi Li; Stefan Bertilsson; Wenlong Zhang; Haolan Wang; Haibing Cong; Haomiao Cheng (Journal of Environmental Management, 2024)

A comparative study of algal-bacterial granular sludges and aerobic granular sludge at different C/N ratio: Granule characteristics, SND progress and Microbial community - Ruiling Bao; Yunlong Zheng; Cong Ma; Lianqing Xue; Wei Cheng; Aidong Ruan; Xiang Li (Journal of Environmental Chemical Engineering, 2024)

An ionic liquid-modified PEDOT/Ti3C2TX based molecularly imprinted electrochemical sensor for pico-molar sensitive detection of L-Tryptophan in milk - Cong Xue; Ruxangul Jamal; Tursun Abdiryim; Xiong Liu; Fangfei Liu; Feng Xu; Qian Cheng; Xinsheng Tang; Nana Fan (Food Chemistry, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Green supply chain for steel raw materials under price and demand uncertainty - Cong Cheng; HongMei Chu; Liang Zhang; LianJie Tang (Journal of Cleaner Production, 2024)

Functional properties and structure of soluble dietary fiber obtained from rice bran with steam explosion treatment - Xin-Yi Tian; Jian-Fu Liu; Cong-Cong Qiao; Zhuo Cheng; Na-Na Wu; Bin Tan (Journal of Cereal Science, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Genome-wide analysis of NAC transcription factors and exploration of candidate genes regulating selenium metabolism in Broussonetia papyrifera - Longfei Guo; Yongling Liao; Shiming Deng; Jitao Li; Xianchen Bu; Changye Zhu; Weiwei Zhang; Xin Cong; Shuiyuan Cheng; Qiangwen Chen; Feng Xu (Planta, 2024)

Bicyclol mitigates lipopolysaccharide-induced acute lung injury through myeloid differentiation factor 88 inhibition - Lili Fu; Linting Cheng; Junliang Lu; Qianru Ye; Cong Shu; Chuchu Sun; Zhiguo Liu; Guang Liang; Weixin Zhao (Toxicology and Applied Pharmacology, 2024)

Triphenyltin chloride exposure inhibits meiotic maturation of mouse oocytes by disrupting cytoskeleton assembly and cell cycle progression - Cong Ma; Hongzhen Ruan; Huiru Cheng; Zuying Xu; Caiyun Wu; Dan Liang; Huifen Xiang; Yunxia Cao; Zhiming Ding (Toxicology in Vitro, 2024)

ROS- and CBF- mediated pathways are involved in chlorophyll degradation and anthocyanin accumulation enhanced by cool temperatures in ripening litchi fruits - Shi-Cheng Zou; Mao-Gen Zhuo; Farhat Abbas; Ren-Fang Zeng; Gui-Bing Hu; Hui-Cong Wang; Xu-Ming Huang (Postharvest Biology and Technology, 2024)

Five undescribed cyclopeptides from Cordyceps militaris - Wei Yang; Cong Fu; Bin-Yuan Hu; Yong-Ming Yan; Yong-Xian Cheng (Phytochemistry, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Light thinning effectively improves forest soil water replenishment in water-limited areas: Observational evidence from Robinia pseudoacacia plantations on the Loess Plateau, China - Xia Liu; Lei Jiao; Dong Cheng; Jianbo Liu; Zongshan Li; Zhaolin Li; Cong Wang; Xiaolong He; Yanchun Cao; Guangyao Gao (Journal of Hydrology, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

Bimetallic iron-copper nanozyme for determination and degradation of norfloxacin in foods - Cong Cheng; Min Han; Gang Xiang; Xiaoying Fu; Xianxing Wang; Changfang Lu (Food Chemistry, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Patterns of crop-specific fertilizer-nitrogen losses and opportunities for sustainable mitigation: A quantitative overview of 15N-tracing studies - Cong Xu; Hanshen Zhu; Haokuang Liu; Cheng Ji; Jie Yuan; Guanlin Li; Jidong Wang; Yongchun Zhang (Soil Ecology Letters, 2024)

Amendment of straw with decomposing inoculants benefits the ecosystem carbon budget and carbon footprint in a subtropical wheat cropping field - Cheng Ji; Jidong Wang; Cong Xu; Yian Gu; Jie Yuan; Dong Liang; Lei Wang; Yunwang Ning; Jie Zhou; Yongchun Zhang (Science of The Total Environment, 2024)

New perspective for Calpain-Mediated regulation of meat Quality: Unveiling the impact on mitochondrial pathway apoptosis in post-mortem - Yunhao Ma; Ying Wang; Zhaoming Wang; Yong Xie; Cheng Tang; Cong Li; Feiran Xu; Hui Zhou; Baocai Xu (Food Chemistry, 2024)

Taxonomic status of hares ( Lepus spp.) in Xinjiang, China (Lagomorpha: Leporidae): An integrative approach - Wen‐Juan Shan; Zu‐Rui Li; Hui‐Ying Dai; Peng‐Cheng Dong; Yu‐Cong Zhang (Zoologica Scripta, 2024)
The taxonomic status and interspecies relationships of hares (genus Lepus ) in Xinjiang, China, remain ambiguous owing to extremely similar external morphologies, introgressive hybridization between species and a lack of molecular genetic records. In this study, a total of 154 hare specimens were used to clarify their taxonomic status. Based on multiple lines of evidence, including observations and comparisons of external morphological characteristics, skull morphometrics and genome‐wide single nucleotide polymorphism (SNP) datasets, four hare species were recognised. Lepus yarkandensis and Lepus timidus , which have obvious morphological characteristics, were identified as two distinct species, as previously reported. Combining the integrated morphological and molecular datasets with the relevant literature, we proposed suggestions on the classification of the more controversial hares. Due to molecular and morphological similarities, hares in northern and central Xinjiang were divided into two subspecies of Lepus tolai , namely, Lepus tolai lehmanni and Lepus tolai centrasiaticus . Despite similar external morphological characters, hares in the southwest Pamir Plateau and its surroundings can be distinguished from L. tolai by differences in skull morphology and genetic divergence and were, therefore, considered a subspecies of Lepus tibetanus , Lepus tibetanus pamirensis . Furthermore, we found that hybridization and introgression occurred between sympatric or parapatric hares, especially between L. yarkandensis and L. tibetanus pamirensis , L. yarkandensis and L. tolai centrasiaticus , and L. tolai lehmanni and L. timidus .

Germplasm evaluation and identification of the population source of hard clam (Mercenaria mercenaria) in China using SSR and COI markers - JunYi Wang; DongXiu Xue; MeiJie Yang; YunLong Ji; Hao Song; Cong Zhou; Pu Shi; YongRen Li; YongJun Guo; FanYu Meng; ChangPing Lai; ShunFeng Cheng; et al. (Frontiers in Marine Science, 2024)
In aquaculture, good germplasm resources are nearly decisive for its development. The hard clam ( Mercenaria mercenaria ), a significant marine aquaculture bivalve in China, has flourished quickly since being introduced from North America in 1997. However, for numerous reasons, it has suffered from germplasm deterioration and uncertain origins. To address these issues, seven microsatellite DNA loci (SSRs) and mtCOI were employed to evaluate germplasm and trace the origins of various Chinese populations. The results of these two molecular genetic markers revealed weak genetic differentiation among all Chinese populations, with high genetic diversity observed across most individuals, except for a few outliers. This suggests an alarming situation regarding germplasm resources in China. Based on results of traceability analysis, the most likely areas of origin for the Chinese populations are Chesapeake Bay and the southern region of Cape Hatteras. This study provides a crucial theoretical foundation for the cultivation, conservation, and subsequent introduction of hard clam populations in China, thereby ensuring the sustainable growth of the hard clam breeding sector.

Quantifying denudation rates and sediment recycling of low-relief, high-elevation landscapes using in-situ and meteoric cosmogenic nuclides - Ye Yang; Shun-Cheng Zhang; Jia-Xin Zhang; Li-Feng Cui; Cong-Qiang Liu; Sheng Xu (Geochimica et Cosmochimica Acta, 2024)

Comparing the sustainability of smallholder and business farms in the North China Plain; a case study in Quzhou - Zhan Xu; Zhengyuan Liang; Jiali Cheng; Jeroen C.J. Groot; Chaochun Zhang; Wen-Feng Cong; Fusuo Zhang; Wopke van der Werf (Agricultural Systems, 2024)

Heavy metal pollution in agricultural soils from surrounding industries with low emissions: Assessing contamination levels and sources - Cong Yao; Yidan Yang; Caixia Li; Zhijie Shen; Jieqin Li; Nan Mei; Chengzhong Luo; Yongmin Wang; Cheng Zhang; Dingyong Wang (Science of The Total Environment, 2024)

Profiling dynamics of the Southeast Asia's largest lake, Tonle Sap Lake - Wenting Jiang; Zhijun Dai; Xuefei Mei; Chuqi Long; Nguyen An Binh; Cong Mai Van; Jinping Cheng (Science of The Total Environment, 2024)

Carbon-negative and high-rate nutrient recovery from municipal wastewater using mixotrophic Scenedesmus acuminatus - Muhammad Mubashar; Rabail Zulekha; Shaozhe Cheng; Cong Xu; Jing Li; Xuezhi Zhang (Journal of Environmental Management, 2024)

Molecular dynamic simulation of H2-CH4 binary hydrate growth induced by methane hydrate - Wenfeng Hu; Xiaoqiang Tian; Cong Chen; Chuanxiao Cheng; Shiquan Zhu; Jun Zhang; Tian Qi; Tingxiang Jin; Xuehong Wu (Fuel, 2024)

Selenium-Enriched Cardamine violifolia Alleviates LPS-Induced Hepatic Damage and Inflammation by Suppressing TLR4/NODs–Necroptosis Signal Axes in Piglets - Dan Wang; Wenshuai Xie; Wensheng He; Huiling Zhu; Yue Zhang; Qingyu Gao; Xin Cong; Shuiyuan Cheng; Yulan Liu (Biological Trace Element Research, 2024)

A slow-release fertilizer containing cyhalofop-butyl reduces N2O emissions by slowly releasing nitrogen and down-regulating the relative abundance of nirK - Zewang Zhang; Gonglei Chen; Xiangyang Yu; Dong Liang; Cong Xu; Cheng Ji; Lei Wang; Hongbo Ma; Jidong Wang (Science of The Total Environment, 2024)

Vertical biome shifts and climate changes since the last glacial maximum in the southeastern margin of the Tibetan plateau, Southwest China - Xiao Zhang; Kangyou Huang; Jun Cheng; Rachid Cheddadi; Qiuchi Wan; Cong Chen; Yongjie Tang; Yuanfu Yue; Xin Jia; Zhuo Zheng (Quaternary Science Reviews, 2024)

Chronological features of Heinrich Stadial 2 based on a high-resolution analysis of δ18O stalagmite records from China, and possible links to changes in Atlantic Meridional Overturning Circulation - Yingfang Cui; Hao Xu; Yijia Liang; Kan Zhao; Jianshun Chen; Yongjin Wang; Jiaqi Cong; Hai Cheng; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Transformation of W/O/W emulsions and O/W/O emulsions for co-loading selenium-enriched peptide and vitamin E: Design and characteristics - Fang Xie; Yuan Fang; Xin Liu; Xin Cong; Yangchao Luo; Jiaojiao Zhou; Zia-ud Din; Shuiyuan Cheng; Jie Cai (Journal of Food Engineering, 2024)

Monodispersed Co-N3 loaded carbon nitride mediated peroxymonosulfate activation for rapid degradation of trace urea via singlet oxygen - Shilong Jiang; Song Cheng; Jiashun Cao; Cailiang Yue; Jianglei Xiong; Cong Jiang; Hongzhan Cai; Jianhua Wu (Chemical Engineering Journal, 2024)

Assessing the impacts of connected-and-autonomous vehicle management strategy on the environmental sustainability of urban expressway system - Cong-jian Liu; Ke Chen; Zhikang Bao; S. Thomas Ng; Cheng Zhang; Ze-hao Jiang (Sustainable Cities and Society, 2023)

Increased productivity of temperate vegetation in the preceding year drives early spring phenology in the subsequent year in northern China - Qi Zhang; Hongfang Zhao; Wanying Cheng; Nan Cong; Xuhui Wang; Hangqi Liang; Xia Li (Science of The Total Environment, 2023)

Farmers perceive diminishing ecosystem services, but overlook dis-services in intensively used agricultural landscapes in the North China Plain - Jiali Cheng; Zhan Xu; Zhengyuan Liang; Fan Li; Wen-Feng Cong; Chaochun Zhang; Lei Song; Chong Wang; Fusuo Zhang; Andries Richter; Wopke van der Werf; Jeroen C.J. Groot (Journal of Environmental Management, 2023)

Mechanism of low-voltage electrostatic fields on the water-holding capacity in frozen beef steak: Insights from myofilament lattice arrays - Yong Xie; Kai Zhou; Bo Chen; Yunhao Ma; Cheng Tang; Peijun Li; Zhaoming Wang; Feiran Xu; Cong Li; Hui Zhou; Baocai Xu (Food Chemistry, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

White matter alterations in mild cognitive impairment revealed by meta-analysis of diffusion tensor imaging using tract-based spatial statistics - Longfei Li; Wei Yang; Yu Wan; Hailong Shen; Ting Wang; Liangliang Ping; Chuanxin Liu; Min Chen; Hao Yu; Shushu Jin; Yuqi Cheng; Xiufeng Xu; et al. (Brain Imaging and Behavior, 2023)

Effects of supplementary thyme on immunity responses, antioxidant indices, rumen enzymes concentrations and rumen bacteria composition in Hu sheep - Xia Du; Xindong Cheng; Kaixi Ji; Abraham Allan Degen; Yanping Liang; Xiukun Wu; Qiaoxia Dong; Mengyu Feng; Dan Jiao; Haitao Cong; Guo Yang (Animal Feed Science and Technology, 2023)

Macroscale composite principal-monotonicity distributed projection of climate-induced hydrologic changes: Tempo-spatial variabilities, and variation decompositions - Guanhui Cheng; Guohe (Gordon) Huang; Qian Tan; Cong Dong; Xiong Zhou (Journal of Hydrology, 2023)

Systemic subchronic toxicity and comparison of four selenium nutritional supplements by 90-day oral exposure in Sprague-Dawley rats - Lu Yu; Yanmei Li; Wen Qu; Yanhua Zheng; Xuejiao Chen; Shaohua Fu; Jingjing Qu; Jie Tian; Shuiyuan Cheng; Xin Cong; Bolin Fan; Chunhong Wang (Food and Chemical Toxicology, 2023)

Faults and gas chimneys jointly dominate the gas hydrate accumulation in the Shenhu Area, northern South China Sea - Jinfeng Ren; Cong Cheng; Tao Jiang; Zenggui Kuang; Hongfei Lai; Jinqiang Liang; Zigui Chen; Tao Li (Frontiers in Marine Science, 2023)
Gas hydrates possess significant potential as an energy resource and exert a notable influence on global climate change. The Shenhu Area is one of the globally recognized focal points for gas hydrate research, and additional investigation is required to fully comprehend its gas migration mechanism. By utilizing the most recent core-log-seismic data and gas geochemical data, a comprehensive analysis was conducted to determine the influence of gas migration pathways on gas hydrate accumulation in the study area. This study investigated the various types of gas migration pathways, employing integrated geological models that incorporate faults and gas chimneys to understand their respective contributions to the accumulation of gas hydrates. Based on these findings and drilling constraints, a three-gas combined production model was subsequently proposed. Thermogenic gas, secondary microbial gas, and in situ microbial gas are all potential sources of the gas responsible for hydrate formation. Thermogenic gas plays a significant role in the gas hydrate system, as evidenced by distinct features of late-mature thermogenic gas observed in gas samples extracted from hydrates in Well W18. In the study area, the primary conduits for gas migration encompass deep faults, branch faults, and gas chimneys. Among these, deep faults act as the most crucial pathways of thermogenic gas migration. The integration of geological models that incorporating deep faults and gas chimneys has profoundly impacted the accumulation of gas hydrates in the Shenhu Area, consequently influencing the distribution of shallow gas and gas hydrate. Furthermore, the proposed three-gas combined production model, which involves the simultaneous extraction of deep gas reservoirs, shallow gas reservoirs, and gas hydrates, holds significant implications for exploring and developing deep-water natural gas resources. However, its successful implementation necessitates interdisciplinary collaboration among scientists.

High performance forward osmosis membrane with ultrathin hydrophobic nanofibrous interlayer - Cong Ma; Zhaoyang Cheng; Meng Zhang; Yukun Huang; Weili Huang; Liang Wang; Bin Zhao; Zhaohui Zhang (Chemosphere, 2023)

Divergent temporal changes of heavy metals in the soil induced by natural versus anthropogenic forces: A case study in the Yangtze River delta area, China - Cheng Wang; Jianhua Wang; Cong Zhong; Yanping Zhao (Science of The Total Environment, 2023)

Wheat adaptation to environmental stresses under climate change: Molecular basis and genetic improvement - Hude Mao; Cong Jiang; Chunlei Tang; Xiaojun Nie; Linying Du; Yuling Liu; Peng Cheng; Yunfeng Wu; Huiquan Liu; Zhensheng Kang; Xiaojie Wang (Molecular Plant, 2023)

Preparation, properties and applications of porous hydrogels containing thiol groups for heavy metal removal - Huai-Yuan Niu; Jin-Cheng Li; Ji-Shan Li; Cong Yi; Cheng-Gang Niu (Journal of Environmental Chemical Engineering, 2023)

Effect of influent ammonia nitrogen concentration on the phosphorus removal process in the aerobic granular sludge reactor - Wei Cheng; Cong Ma; Ruiling Bao; Xiaoli Yang; Xuankai Zhou; Yan Liu; Qing Liu; Aidong Ruan; Xiang Li (Journal of Environmental Chemical Engineering, 2023)

Quantitative characterization of water transport and wetting patterns in coal using LF-NMR and FTIR techniques - Yuliang Cai; Cheng Zhai; Xu Yu; Yong Sun; Jizhao Xu; Yangfeng Zheng; Yuzhou Cong; Yujie Li; Aikun Chen; Hexiang Xu; Shuai Wang; Xizhuo Wu (Fuel, 2023)

Contamination characteristics and potential health risk of brominated flame retardants in paddy soils and rice plants around a typical e-waste recycling site in south China - Kailun Luo; Zhihua Qiao; Weiyu Liang; Cong Lu; Mengru Fu; Shanqi Zhou; Yanna Han; Cheng Peng; Wei Zhang (Environmental Pollution, 2023)

Extremely stable deep-blue organic light-emitting diodes employing diindolophenazine-based fluorophore with narrow-band emission and a shallow LUMO level - Cong Cheng; Yunhui Zhu; Taiju Tsuboi; Chao Deng; Weiwei Lou; Tiangeng Liu; Dan Wang; Qisheng Zhang (Chemical Engineering Journal, 2023)

NaNO2 additive-assisted Li2O2 decomposition for highly efficient cathode prelithiation of lithium-ion batteries - Rang Xiao; Cong Kang; Yang Ren; Renlong Li; Jiyuan Jian; Binghan Cui; Geping Yin; Xinqun Cheng; Yulin Ma; Hua Huo; Pengjian Zuo; Guokang Han; et al. (Chemical Engineering Journal, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

A tradeoff between denitrification and nitrate leaching into the subsoil in nitrate-rich vegetable soils treated by reductive soil disinfestation - Hui-Min Zhang; Yu Liu; Ying-Hua Zhang; Yong Li; Zhao-Xiong Chen; Xin Sun; Hang Jing; Jing Wang; Ahmed S. Elrys; Mao-Heng Zhang; Zu-Cong Cai; Yi Cheng (Agriculture, Ecosystems & Environment, 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

Designing diversified crop rotations to advance sustainability: A method and an application - Zhengyuan Liang; Zhan Xu; Jiali Cheng; Bowen Ma; Wen-Feng Cong; Chaochun Zhang; Fusuo Zhang; Wopke van der Werf; Jeroen C.J. Groot (Sustainable Production and Consumption, 2023)

Parallel paired electrolysis-enabled asymmetric catalysis: simultaneous synthesis of aldehydes/aryl bromides and chiral alcohols - Bing Sun; Zhen-Hua Wang; Yun-Zhao Wang; Yu-Cheng Gu; Cong Ma; Tian-Sheng Mei (Science Bulletin, 2023)

Loss of OsARF18 function confers glufosinate resistance in rice - Jin-Qiu Xia; Da-Yu He; Qin-Yu Liang; Zheng-Yi Zhang; Jie Wu; Zi-Sheng Zhang; Jing Zhang; Lin Wang; Cong-He Zhang; Ping-Xia Zhao; Cheng-Bin Xiang (Molecular Plant, 2023)

Fractionations of heavy metals and their correlations with magnetic susceptibility in soil from a typical alluvial island in the lower yangtze river, China - Cheng Wang; Rong Ma; Jianhua Wang; Cong Zhong; Yanping Zhao; Patrick Browne (Journal of Cleaner Production, 2023)

Mechanism behind the deterioration in gel properties of collagen gel induced by high-temperature treatments: A molecular perspective - Cheng Tang; Yujuan Xu; Kai Zhou; Yong Xie; Yunhao Ma; Cong Li; Feiran Xu; Hui Zhou; Baocai Xu (Food Research International, 2023)

Carbendazim exposure inhibits mouse oocytes meiotic maturation in vitro by destroying spindle assembly - Cong Ma; Zhuonan Yang; Shouxin Zhang; Xueke Zhang; Siyuan Wang; Huiru Cheng; Yang Liu; Hongzhen Ruan; Zuying Xu; Chunmei Liang; Dan Liang; Zhiming Ding; et al. (Food and Chemical Toxicology, 2023)

Selenium-enriched Cardamine violifolia protects against sepsis-induced intestinal injury by regulating mitochondrial fusion in weaned pigs - Dan Wang; Yanling Kuang; Qingqing Lv; Wenshuai Xie; Xiao Xu; Huiling Zhu; Yue Zhang; Xin Cong; Shuiyuan Cheng; Yulan Liu (Science China Life Sciences, 2023)

Activation of Cannabinoid Receptor 1 in GABAergic Neurons in the Rostral Anterior Insular Cortex Contributes to the Analgesia Following Common Peroneal Nerve Ligation - Ming Zhang; Cong Li; Qian Xue; Chang-Bo Lu; Huan Zhao; Fan-Cheng Meng; Ying Zhang; Sheng-Xi Wu; Yan Zhang; Hui Xu (Neuroscience Bulletin, 2023)
The rostral agranular insular cortex (RAIC) has been associated with pain modulation. Although the endogenous cannabinoid system (eCB) has been shown to regulate chronic pain, the roles of eCBs in the RAIC remain elusive under the neuropathic pain state. Neuropathic pain was induced in C57BL/6 mice by common peroneal nerve (CPN) ligation. The roles of the eCB were tested in the RAIC of ligated CPN C57BL/6J mice, glutamatergic, or GABAergic neuron cannabinoid receptor 1 (CB1R) knockdown mice with the whole-cell patch-clamp and pain behavioral methods. The E/I ratio (amplitude ratio between mEPSCs and mIPSCs) was significantly increased in layer V pyramidal neurons of the RAIC in CPN-ligated mice. Depolarization-induced suppression of inhibition but not depolarization-induced suppression of excitation in RAIC layer V pyramidal neurons were significantly increased in CPN-ligated mice. The analgesic effect of ACEA (a CB1R agonist) was alleviated along with bilateral dorsolateral funiculus lesions, with the administration of AM251 (a CB1R antagonist), and in CB1R knockdown mice in GABAergic neurons, but not glutamatergic neurons of the RAIC. Our results suggest that CB1R activation reinforces the function of the descending pain inhibitory pathway via reducing the inhibition of glutamatergic layer V neurons by GABAergic neurons in the RAIC to induce an analgesic effect in neuropathic pain.

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Degradation efficiency of antibiotics by the sewage-fed microbial fuel cells depends on gram-staining property of exoelectrogens - Peng Cheng; Cong Yang; Shang Zhou; Junyu Huang; Rongrong Liu; Bing Yan (Process Safety and Environmental Protection, 2023)

Experimental study on tail cavity structure and pressure characteristics of underwater vehicle with tail jet - Qian Yang; Yulin Wang; Yinjie Wei; Cong Wang; Shaohua Cheng (Ocean Engineering, 2023)

Effect of acid concentration on organic structure and small molecule stripping of coal during acid treatment and electrolysis for hydrogen production - Cong Chen; Jianzhong Liu; Jianbin Wang; Dedi Li; Yitong Chen; Jun Cheng (Fuel, 2023)

Mechanism of textural properties changes of cooked chicken in early postmortem: Effect of protein degradation induced by calpain on heating shrinkage - Yunhao Ma; Ying Wang; Zhaoming Wang; Bo Chen; Yong Xie; Cheng Tang; Cong Li; Kai Zhou; Hui Zhou; Baocai Xu (Food Chemistry, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Sand-rich Pleistocene deep-water channels and their implications for gas hydrate accumulation: Evidence from the Qiongdongnan Basin, northern South China Sea - Cong Cheng; Tao Jiang; Zenggui Kuang; Hongfei Lai; Jinqiang Liang; Jinfeng Ren; Zigui Chen; Yue Chen; Tao Li; Pengfei Xiong (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Combined GSK-3β and MEK inhibitors modulate the stemness and radiotherapy sensitivity of cervical cancer stem cells through the Wnt signaling pathway - Cong Wang; Lijun Liu; Yan Cheng; Huirong Shi (Chemico-Biological Interactions, 2023)

Investigate the effects of urban land use on PM2.5 concentration: An application of deep learning simulation - Liyuan Zhao; Ming Zhang; Si Cheng; Yunhao Fang; Shuxian Wang; Cong Zhou (Building and Environment, 2023)

Developmental and cardiac toxicity assessment of Ethyl 3-(N-butylacetamido) propanoate (EBAAP) in zebrafish embryos - Qiang Luo; Liping Ai; Shuqiong Tang; Hua Zhang; Jinze Ma; Xiaoping Xiao; Keyuan Zhong; Guiyou Tian; Bo Cheng; Cong Xiong; Xiaobei Chen; Huiqiang Lu (Aquatic Toxicology, 2023)

The Effect of Short-Term Air Pollutants Exposure on Daily Mortality Among Elderly Individuals in China: A Systematic Review and Meta-Analysis - Cong Liu; Fengwei Jia; Mengmeng Ji; Guofeng Qu; Chunping Ye; Jiali Cheng; Andiara Schwingel; Rong Gao (Water, Air, & Soil Pollution, 2023)
To systematically review the literature regarding the effect of air pollutants on the excess mortality risk among the elderly Chinese. PubMed, Scopus, Web of Science (WOS), and Chinese National Knowledge Infrastructure (CNKI) electronic databases were searched. A standardized data extraction form was used to collect methodological and outcome variables from each eligible study. The effect value was combined with a fixed- or random-effect model, and sensitivity analysis and publication bias test were performed. A total of 26 articles on air pollutants and excess risk (ER) of mortality in the Chinese elderly were identified. Among them, 16, 14, 8, and 8 articles contained PM 2.5 , PM 10 , SO 2 , and NO 2 data, respectively. The meta-analysis results showed that the excess risk of mortality in the Chinese elderly associated with per 10 µg/m 3 increase in PM 2.5 , PM 10 , SO 2 , and NO 2 concentrations was 1.01%, 0.54%, 1.06%and 1.35%, respectively. Sufficient evidence supports that the increase in air pollutants (PM 2.5 , PM 10 , SO 2 , and NO 2 ) will escalate the mortality of the elderly in China. Future research can study two or more air pollution models and the impact of air pollution on elderly mortality rates under different temperatures, duration of exposure, seasons and regions.

Pore Structure and Damage Evaluation of Hot Dry Rocks in Enhanced Geothermal System by Combining Electrical Resistivity, Ultrasonic Waves and Nuclear Magnetic Resonance - Yong Sun; Cheng Zhai; Xu Yu; Jizhao Xu; Yuzhou Cong; Yangfeng Zheng; Wei Tang; Yujie Li (Natural Resources Research, 2023)

Biochar supported nanoscale zero-valent iron for the kinetics removal and mechanism of decabromodiphenyl ethane in the sediment - Cong Lu; Xuan Zhao; Zhihua Qiao; Kailun Luo; Shanqi Zhou; Mengru Fu; Cheng Peng; Wei Zhang (Environmental Science and Pollution Research, 2023)

Functional metabolism pathways of significantly regulated genes in Nannochloropsis oceanica with various nitrogen/phosphorus nutrients for CO2 fixation - Lingchong Feng; Zhenyi Wang; Dongwei Jia; Xiangbo Zou; Mumin Rao; Zhimin Huang; Cao Kuang; Ji Ye; Chuangting Chen; Cong Huang; Maoqiang Zhang; Jun Cheng (Science of The Total Environment, 2023)

Utilization of constructed wetland technology in China's sponge city scheme under carbon neutral vision - Yamei Cai; Yaqian Zhao; Ting Wei; Wei Fu; Cheng Tang; Yujie Yuan; Qi Yin; Cong Wang (Journal of Water Process Engineering, 2023)

Enrichment strategies of heavy metals in the O/H/O process composed of biological fluidized bed for wastewater treatment: A case study of Cu and Zn - Cong Wei; Xiaoqian Cheng; Wei Sun; Xia Tang; Tuo Wei; Zijun Pang; Xiong Ke; Zhi Qin; Jiamin Pan; Gengrui Wei; Guanglei Qiu; Chunhua Feng; et al. (Journal of Cleaner Production, 2023)

Field, plant, to leaf: A meta-analysis on crop water use efficiency response to potassium fertilization - Cheng Yang; Wanyang Zhang; Hehe Gu; Aihua Liu; Qi Guo; Yizhou Chen; Jianwei Lu; Tao Ren; Rihuan Cong; Zhifeng Lu; Yangyang Zhang; Shipeng Liao; et al. (Journal of Hydrology, 2023)

Geochemical distribution and mineralogy of heavy metals in the gasification residue of coal-waste activated carbon-slurry: Insights into leaching behavior - Jianbin Wang; Jianzhong Liu; Dedi Li; Cong Chen; Jun Cheng (Journal of Hazardous Materials, 2023)

Ag-modification argyrodite electrolytes enable high-performance for all-solid-state lithium metal batteries - Zhongkai Wu; Chuang Yu; Chaochao Wei; Ziling Jiang; Cong Liao; Shuai Chen; Shaoqing Chen; Linfeng Peng; Shijie Cheng; Jia Xie (Chemical Engineering Journal, 2023)

Microstructure Evolution of Bituminous Coal Modified by High-Pressure CO2 Foam Fracturing Fluid with Different Treatment Times - Yangfeng Zheng; Cheng Zhai; Aikun Chen; Yong Sun; Yuzhou Cong; Wei Tang; Jizhao Xu; Xu Yu; Xinyu Zhu; Yujie Li (Natural Resources Research, 2023)

Machine-learning-aided application of high-gravity technology to enhance ammonia recovery of fresh waste leachate - Shaomin Guo; Xiuwei Ao; Xin Ma; Shikun Cheng; Cong Men; Hidenori Harada; Devendra P. Saroj; Heinz-Peter Mang; Zifu Li; Lei Zheng (Water Research, 2023)

Holocene warming and evergreen/deciduous forest replacement across eastern China - Zhuo Zheng; Cong Chen; Kangyou Huang; Xiao Zhang; Peter Kershaw; Jun Cheng; Jie Li; Yuanfu Yue; Qiuchi Wan; Yaze Zhang; Yongjie Tang; Mengyuan Wang; et al. (Quaternary Science Reviews, 2023)

Prediction of the ash melting behavior and mineral phase transformation during the co-gasification of waste activated carbon and coal water slurry - Jianbin Wang; Jianzhong Liu; Cong Chen; Hanjing Lv; Jun Cheng (Fuel, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Evaluation of the Added Value of Probabilistic Nowcasting Ensemble Forecasts on Regional Ensemble Forecasts - Lu Yang; Cong-Lan Cheng; Yu Xia; Min Chen; Ming-Xuan Chen; Han-Bin Zhang; Xiang-Yu Huang (Advances in Atmospheric Sciences, 2023)

Experimental study on temperature attenuation of smoke flow driven by dual fire sources in a tunnel - Kun He; Long Shi; Shaogang Zhang; Wei Cong; Hui Yang; Xudong Cheng (Tunnelling and Underground Space Technology, 2023)

CO2 gradient domestication improved high-concentration CO2 tolerance and photoautotrophic growth of Euglena gracilis - Kai Xin; Ruhan Guo; Xiangbo Zou; Mumin Rao; Zhimin Huang; Cao Kuang; Ji Ye; Chuangting Chen; Cong Huang; Maoqiang Zhang; Weijuan Yang; Jun Cheng (Science of The Total Environment, 2023)

Quantification of Asian monsoon variability from 68 ka BP through pollen-based climate reconstruction - Xiao Zhang; Zhuo Zheng; Kangyou Huang; Jun Cheng; Rachid Cheddadi; Yan Zhao; Chen Liang; Xiaoqiang Yang; Qiuchi Wan; Yongjie Tang; Cong Chen; Jie Li (Science Bulletin, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Performance and degradation mechanism of phycocyanin by Cu-TiO2 photocatalytic treatment - Yuan-yuan Ren; Cheng Liu; Zhen Cao; Cong-cong Li (Environmental Science and Pollution Research, 2023)

A Hybrid Multi-Criteria Decision-Making Framework for Ship-Equipment Suitability Evaluation Using Improved ISM, AHP, and Fuzzy TOPSIS Methods - Cheng Chen; Xiangrui Zhang; Guo Wang; Feng Feng; Cong Sun; Qin He (Journal of Marine Science and Engineering, 2023)
The inherent complexity of large ships makes it challenging to evaluate ship designs systematically and scientifically. Knowledge-based expert systems can be reasonable solutions. However, this problem needs more rationality and better operability, especially in complicated ship-equipment suitability evaluation problems with numerous indicators and complex structures. This paper presents a hybrid multi-criteria decision-making (MCDM) framework to extend the ship-equipment suitability evaluation to group decision-making settings, where individual consistency and group consensus are thoroughly investigated to improve rationality and operability. As a result, an improved Interpretive Structural Modeling (ISM) method is developed to construct the evaluation index systems. Furthermore, based on an applicability analysis of the selected MCDM methods, an improved Analytical Hierarchy Process (AHP) method is proposed to distribute the index weights, and an applicable Fuzzy Technique for Order Preference by Similarity to Ideal Solution (Fuzzy TOPSIS) method is utilized to evaluate and select appropriate ship designs. Finally, a ship-equipment environmental suitability evaluation case is examined. The results indicate that the proposed framework improves the rationality and operability of the decision-making process and provides practical support to decision-makers for the systematic and scientific evaluation of ship designs. Therefore, it can also be applied to other ship design evaluation and selection problems.

Fertilizer N triggers native soil N-derived N2O emissions by priming gross N mineralization - Cong Xu; Hanshen Zhu; Jing Wang; Cheng Ji; Yaobin Liu; Danyan Chen; Hui Zhang; Jidong Wang; Yongchun Zhang (Soil Biology and Biochemistry, 2023)

Tracing and quantifying the source of heavy metals in agricultural soils in a coal gangue stacking area: Insights from isotope fingerprints and receptor models - Cong Yao; Zhijie Shen; Yongmin Wang; Nan Mei; Caixia Li; Yajun Liu; Weibin Ma; Cheng Zhang; Dingyong Wang (Science of The Total Environment, 2023)

Purification performance from bypass ecological treatment systems treating WWTPs effluents and improvement of water quality in receiving rivers: A case study in southern China - Xiaoxu Zheng; Shengjun Xu; Yeliang Bi; Gong Cheng; Shuanglong Ma; Hao Zhang; Cancan Jiang; Cong Wang; Ping Lyu; Yu Qin; Xuliang Zhuang (Journal of Environmental Management, 2023)

Middle Jurassic palaeoclimate changes within the central Ordos Basin based on palynological records - Zenglian Xu; Yinhang Cheng; Cong Ao; Tianfu Zhang; Shaoyi Wang (Palaeobiodiversity and Palaeoenvironments, 2023)

Associations between short-term and long-term exposure to particulate matter and preterm birth - Yun-Fei Su; Cheng Li; Jing-Jing Xu; Fang-Yue Zhou; Tao Li; Cong Liu; Yan-Ting Wu; He-Feng Huang (Chemosphere, 2023)

Pulsed light improved the shelf life of apricot （after simulated long-distance air transportation） by regulating cell wall metabolism - Xiaowen Hua; Tingting Li; Caie Wu; Dandan Zhou; Gongjian Fan; Xiaojing Li; Kaiping Cong; Zhicheng Yan; Xin Cheng (Postharvest Biology and Technology, 2023)

Functionalization process of coking sludge: Biochar immobilizing with Fe/Co to enhance the wastewater treatment of ozone - Jiamin Pan; Zijun Pang; Tuo Wei; Xiong Ke; Cong Wei; Xiaoqian Cheng; Zhi Qin; Yun Hu; Chaohai Wei; Fusheng Li (Journal of Water Process Engineering, 2023)

Remanufacturing authorization strategies under consumer brand loyalty - Shanshan Lv; Mengjin Guo; Cong Cheng; Dali Huang (Journal of Cleaner Production, 2023)

Environmental fate of five brominated flame retardants co-exposure in a water-sediment-zebrafish microcosm system: Enrichment, removal, and metabolism mechanisms - Zhihua Qiao; Yawen Wang; Cong Lu; Siyuan Ling; Shanqi Zhou; Mengru Fu; Kailun Luo; Cheng Peng; Wei Zhang; Bingsheng Zhou (Journal of Cleaner Production, 2023)

Role of interfacial electron transfer reactions on sulfamethoxazole degradation by reduced nontronite activating H2O2 - Hao-Jie Cui; Yaqi Ning; Cong Wu; Wei Peng; Dong Cheng; Lichu Yin; Weijun Zhou; Wenjuan Liao (Journal of Environmental Sciences, 2023)

Eco-friendly recyclable high performance ramie yarn reinforced polyimine vitrimer composites - Pandeng Li; Cheng Hao; Huihui Wang; Tian He; Tong Shu; Cong Li; Longjiang Yu; Ning Yan (Chemical Engineering Journal, 2023)

Integrated process for zero discharge of coking wastewater: A hierarchical cycle-based innnovation - Xiong Ke; Tuo Wei; Gengrui Wei; Acong Chen; Xiaoqian Cheng; Zemin Li; Zhi Qin; Zijun Pang; Jiamin Pan; Yao Chen; Cong Wei; Xianghong Guan; et al. (Chemical Engineering Journal, 2023)

A microcosm of modern crust formation: Evidence from zircon ages, Hf O and Nd Sr isotopes and bulk geochemistry of the Menglian Batholith, SE Tibet - Ren-Zhi Zhu; Shao-Cong Lai; Mike Fowler; Jin-Cheng Xie; Sarah M. Glynn (Chemical Geology, 2023)

Sedimentary characteristics and genetic mechanism of the giant ancient pockmarks in the Qiongdongnan Basin, northern South China Sea - Pengfei Xiong; Cong Cheng; Zenggui Kuang; Jinfeng Ren; Jinqiang Liang; Hongfei Lai; Zigui Chen; Jiang Lu; Xiaoyu Fang; Tao Jiang (Acta Oceanologica Sinica, 2023)

Spatiotemporal variations of tidal flat landscape patterns and driving forces in the Yangtze River Delta, China - Shuo Cheng; Xu Zeng; Zihan Wang; Cong Zeng; Ling Cao (Frontiers in Marine Science, 2023)
As a crucial coastal wetland habitat in the transition zone between land and sea, global tidal flats have severely declined by 16% over the last two decades under the dual threats of intense human activities and climate change. The Yangtze River Delta of China, the largest estuary in the western Pacific Ocean, has abundant mudflat resources and a dense human population. It also has some of the most prominent conflicts between economic development and ecological conservation. The current lack of understanding of landscape patterns and influencing factors of the Yangtze River Delta mudflats has severely hampered the region’s ecological conservation and restoration efforts. Based on Landsat time-series images, this study generated a 30-m spatial resolution map of mudflats in the Yangtze River Delta, which shrank by 47% during 1990–2020, with a higher density of mudflat loss in Yancheng and Nantong cities of the Jiangsu province and Hangzhou, Shaoxing, and Ningbo cities of the Zhejiang province. Landscape indices, such as the patch density of tidal flats, have gradually changed since 2000, with most of them showing significant changes in 2010. Mudflats in Lianyungang, northwestern Yancheng, Nanhui, Jiaxing, and Hangzhou showed sharp negative changes in landscape characteristics. Natural and anthropogenic factors had synergistic effects on the above changes in mudflat landscape patterns in the Yangtze River Delta. Mudflat landscape features were mainly influenced by population growth, economic development, reclamation, sediment discharge, and air temperature. Based on the evolving characteristics of mudflat landscape patterns, we recommend improving mudflat landscape management and planning by strengthening mudflat policies, laws, and regulations, developing countermeasures against threats from major stressors, and enhancing the effectiveness of nature reserves for mudflat protection.

Experimental study on temperature characteristics in a subway train carriage with lateral openings in a longitudinally ventilated tunnel - Wei Cong; Kun He; Hui Yang; Long Shi; Xudong Cheng (Tunnelling and Underground Space Technology, 2023)

Description of a moderately acidotolerant and aerotolerant anaerobic bacterium Acidilutibacter cellobiosedens gen. nov., sp. nov. within the family Acidilutibacteraceae fam. nov., and proposal of Sporanaerobacteraceae fam. nov. and Tepidimicrobiaceae fam. nov. - Hui Fan; Jiang Li; Weidong Wu; Rui Chen; Min Yang; Yinggang Zhang; Lulu Cong; Lirong Dai; Yu Deng; Lei Cheng; Shichun Ma (Systematic and Applied Microbiology, 2023)

Development of a macroscale distributed hydro-modeling method: Bayesian principal-monotonicity inference - Guanhui Cheng; Guohe (Gordon) Huang; Cong Dong (Journal of Hydrology, 2023)

Ambient heat stress and urolithiasis attacks in China: Implication for climate change - Lu Zhou; Renjie Chen; Cheng He; Cong Liu; Jian Lei; Yixiang Zhu; Ya Gao; Haidong Kan; Jianwei Xuan (Environmental Research, 2023)

Have China’s drylands become wetting in the past 50 years? - Yu Zhang; Yangjian Zhang; Liang Cheng; Nan Cong; Zhoutao Zheng; Ke Huang; Jianshuang Zhang; Yixuan Zhu; Jie Gao; Yihan Sun (Journal of Geographical Sciences, 2023)

The sub-cellular distribution of Zn and trace elements in the wheat grain: in situ imaging using a NanoSIMS - Cheng Wang; Yunlang Lu; Jianhua Wang; Cong Zhong (Cereal Research Communications, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Cytokine storm and targeted therapy in hemophagocytic lymphohistiocytosis - Han-qi Zhang; Si-Wei Yang; Yi-Cheng Fu; Ming-Cong Chen; Cheng-Hao Yang; Ming-Hua Yang; Xiao-Dan Liu; Qing-Nan He; Hua Jiang; Ming-Yi Zhao (Immunologic Research, 2022)

Initiation Mechanism of Loess Mudflows by Flume Experiments - Penghui Ma; Jianbing Peng; Jianqi Zhuang; Xinghua Zhu; Cong Liu; Yuxiang Cheng; Zuopeng Zhang (Journal of Earth Science, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Research on the layout optimization and utilization of floor gas extraction roadway: a case study in Shoushan No.1 Coal Mine, China - Xiong Ding; Cheng Zhai; Jizhao Xu; Xu Yu; Yong Sun; Yuzhou Cong; Yangfeng Zheng; Wei Tang (Arabian Journal of Geosciences, 2022)

Global patterns of soil gross immobilization of ammonium and nitrate in terrestrial ecosystems - Ahmed S. Elrys; Zhaoxiong Chen; Jing Wang; Yves Uwiragiye; Ayman M. Helmy; El‐Sayed M. Desoky; Yi Cheng; Jin‐bo Zhang; Zu‐cong Cai; Christoph Müller (Global Change Biology, 2022)
Microbial nitrogen (N) immobilization, which typically results in soil N retention but based on the balance of gross N immobilization over gross N production, affects the fate of the anthropogenic reactive N. However, global patterns and drivers of soil gross immobilization of ammonium (I NH4 ) and nitrate (I NO3 ) are still only tentatively known. Here, we provide a comprehensive analysis considering gross N production rates, soil properties, and climate and their interactions for a deeper understanding of the patterns and drivers of I NH4 and I NO3 . By compiling and analyzing 1966 observations from 274 15 N‐labelled studies, we found a global average of I NH4 and I NO3 of 7.41 ± 0.72 and 2.03 ± 0.30 mg N kg −1 day −1 with a ratio of I NO3 to I NH4 (I NO3 :I NH4 ) of 0.79 ± 0.11. Soil I NH4 and I NO3 increased with increasing soil gross N mineralization (GNM) and nitrification (GN), microbial biomass, organic carbon, and total N and decreasing soil bulk density. Our analysis revealed that GNM and GN were the main stimulators for I NH4 and I NO3 , respectively. The structural equation modeling showed that higher soil microbial biomass, total N, pH, and precipitation stimulate I NH4 and I NO3 through enhancing GNM and GN. However, higher temperature and soil bulk density suppress I NH4 and I NO3 by reducing microbial biomass and total N. Soil I NH4 varied with terrestrial ecosystems, being greater in grasslands and forests, which have higher rates of GNM, than in croplands. The highest I NO3 :I NH4 was observed in croplands, which had higher rates of GN. The global average of GN to I NH4 was 2.86 ± 0.31, manifesting a high potential risk of N loss. We highlight that anthropogenic activities that influence soil properties and gross N production rates likely interact with future climate changes and land uses to affect soil N immobilization and, eventually, the fate of the anthropogenic reactive N.

Oral Enrichment of Streptococcus and its Role in Systemic Inflammation Related to Monocyte Activation in Humans with Cocaine Use Disorder - Xiaoyu Fu; Da Cheng; Zhenwu Luo; Amanda Wagner; Sylvia Fitting; Xiaomei Cong; Wanli Xu; Kendra Maas; Zhuang Wan; Jian Zhu; Zejun Zhou; William W. Stoops; et al. (Journal of Neuroimmune Pharmacology, 2022)

Development of eco‐industrial parks in Ethiopia: The case of Hawassa Industrial Park - Doryn Negesa; Wei Cong; Lei Cheng; Lei Shi (Journal of Industrial Ecology, 2022)
As win‐win solutions at the park level, eco‐industrial parks (EIPs) have become the mainstream model to realize a sustainable transition of industrial parks in the world. However, few cases have been implemented in Africa, even though Africa is fertile ground for the growth of industrial parks. This study explores the transition process and outcome of a typical African industrial park—Hawassa Industrial Park (HIP) in Ethiopia. We adopted the international framework for EIPs and applied the strategic niche management (SNM) framework to uncover the transition performance and process. This study shows that HIP's development is a clear articulation of implementing the sustainable development strategy and the industrial park development corporation's role. However, the analysis also identified limitations such as the impracticability of certain framework criteria and inapplicable indicators. Although HIP is still at the nascent stages of EIP implementation, we have found three critical factors for EIP development in Ethiopia from our preliminary observation. These include the importance of actors, the learning process, and having standards for an indicator system. These indicators are of exceptional value to Ethiopian researchers and practitioners in integrating sustainability into local economic development.

Multiple Protein Subcellular Locations Prediction Based on Deep Convolutional Neural Networks with Self-Attention Mechanism - Hanhan Cong; Hong Liu; Yi Cao; Yuehui Chen; Cheng Liang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Community Competition Is the Microorganism Feedback to Sedimentary Carbon Degradation Process in Aquaculture Tidal Flats - Min Zhou; Fu-Tao Fang; Cong Zeng; Li-Hong Zhang; Cheng-Xu Zhou; Zhuo-Yi Zhu (Frontiers in Marine Science, 2022)
How the microbial community response to carbon degradation is unclear, while it plays an essential role in predicting microbial community shift and determining carbon cycling. Surface sediments in two contrasting aquacultural tidal flat sites in Fujian Province, China, were collected in October, 2020. In addition to 16s rRNA gene high-throughput sequencing for determining bacteria and archaea biodiversity, an amino acids-based molecular degradation index DI was used to quantify the carbon degradation status. The results revealed that the microorganism response to DI at the family level was community competition. Specifically, the winning microbes that grew under carbon degradation (i.e., operational taxa unit numbers negatively related with the degradation index) accounted for only 18% of the total family number, but accounted for 54% of the total operational taxa unit numbers. Network analysis confirmed the oppressive relation between winners and the rest (losers + centrists), and further suggested the losers survival strategy as uniting the centrists. These findings shed new light on microorganism feedback to carbon degradation, and provide a scientific basis for the explanation of microbial community shift under progressive carbon degradation.

Age, origin and tectonic implications of Late Carboniferous-Early Permian felsic magmatic rocks from central Inner Mongolia, south-eastern Central Asian Orogenic Belt - Jianzhou Tang; Jian Cheng; Zhicheng Zhang; Jinzhuang Xue; Bo Liu; Tiejun Duan; Weijia Zhan; Cong Ding; Qi Wang; Huaihui Zhang; Yunxi Meng (International Geology Review, 2022)

Investigation on the characteristics of gut microbiota in critically endangered blue-crowned laughingthrush (Garrulax courtoisi) - Cong Wang; Jiawei Li; Yuwei Cheng; Hongbo Tang; Yanpeng Xiong; Yongfei Wu; Luping Wang; Daoqiang Liu; Jianhua Huang (Molecular Genetics and Genomics, 2022)

Damage and Failure of Hot Dry Rock under Cyclic Liquid Nitrogen Cold Shock Treatment: A Non-destructive Ultrasonic Test Method - Yong Sun; Cheng Zhai; Jizhao Xu; Xu Yu; Yuzhou Cong; Yangfeng Zheng; Wei Tang; Yujie Li (Natural Resources Research, 2022)

Pre-inoculation with Bradyrhizobium japonicum confers NaCl tolerance by improving nitrogen status and ion homeostasis in wild soybean (Glycine soja L.) seedlings - Ying Wang; Cong Cheng; Ziyi Du; Bingjun Yu (Acta Physiologiae Plantarum, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Isolation and partial characterization of a novel bacteriocin from Pseudomonas azotoformans with antimicrobial activity against Pasterella multocida - Yu Wang; Shuang Lei; Inam Muhammad; Yu Jia; Cheng-guang He; Yi-Ming Wang; Yun-Hang Gao; Ling-Cong Kong; Hong-Xia Ma (Archives of Microbiology, 2022)

Spatial and temporal fluctuation of rainfall and drought in Balochistan province, Pakistan - Muhammad Rafiq; Yue Cong Li; Yanpei Cheng; Ghani Rahman; Ikram Ullah; Ahmad Ali (Arabian Journal of Geosciences, 2022)

c-Abl Tyrosine Kinase-Mediated Neuronal Apoptosis in Subarachnoid Hemorrhage by Modulating the LRP-1-Dependent Akt/GSK3β Survival Pathway - Cong Yan; Hongwei Yu; Yao Liu; Pei Wu; Chunlei Wang; Hongbo Zhao; Kongbin Yang; Qi Shao; Yingqiang Zhong; Wenyang Zhao; Jingwei Li; Nan Liu; et al. (Journal of Molecular Neuroscience, 2021)

Global gross nitrification rates are dominantly driven by soil carbon‐to‐nitrogen stoichiometry and total nitrogen - Ahmed S. Elrys; Jing Wang; Mohamed A. S. Metwally; Yi Cheng; Jin‐Bo Zhang; Zu‐Cong Cai; Scott X. Chang; Christoph Müller (Global Change Biology, 2021)
Soil gross nitrification (GN) is a critical process in the global nitrogen (N) cycle that results in the formation of nitrate through microbial oxidation of ammonium or organic N, and can both increase N availability to plants and nitrous oxide emissions. Soil GN is thought to be mainly controlled by soil characteristics and the climate, but a comprehensive analysis taking into account the climate, soil characteristics, including microbial characteristics, and their interactions to better understand the direct and indirect controlling factors of GN rates globally is lacking. Using a global meta‐analysis based on 901 observations from 330 15 N‐labeled studies, we show that GN differs significantly among ecosystem types, with the highest rates found in croplands, in association with higher pH which stimulates nitrifying bacteria activities. Autotrophic and heterotrophic nitrifications contribute 63% and 37%, respectively, to global GN. Soil GN increases significantly with soil total N, microbial biomass, and soil pH, but decreases significantly with soil carbon (C) to N ratio (C:N). Structural equation modeling suggested that GN is mainly controlled by C:N and soil total N. Microbial biomass and pH are also important factors controlling GN and their effects are similar. Precipitation and temperature affect GN by altering C:N and/or soil total N. Soil total N and temperature drive heterotrophic nitrification, whereas C:N and pH drive autotrophic nitrification. Moreover, GN is positively related to nitrous oxide and carbon dioxide emissions. This synthesis suggests that changes in soil C:N, soil total N, microbial population size, and/or soil pH due to anthropogenic activities may influence GN, which will affect nitrate accumulation and gaseous emissions of soils under global climate and land‐use changes.

Patterns and drivers of global gross nitrogen mineralization in soils - Ahmed S. Elrys; Ahmad Ali; Huimin Zhang; Yi Cheng; Jinbo Zhang; Zu‐Cong Cai; Christoph Müller; Scott X. Chang (Global Change Biology, 2021)
Soil gross nitrogen (N) mineralization (GNM), a key microbial process in the global N cycle, is mainly controlled by climate and soil properties. This study provides for the first time a comprehensive analysis of the role of soil physicochemical properties and climate and their interactions with soil microbial biomass (MB) in controlling GNM globally. Through a meta‐analysis of 970 observations from 337 published papers from various ecosystems, we found that GNM was positively correlated with MB, total carbon, total N and precipitation, and negatively correlated with bulk density (BD) and soil pH. Our multivariate analysis and structural equation modeling revealed that GNM is driven by MB and dominantly influenced by BD and precipitation. The higher total N accelerates GNM via increasing MB. The decrease in BD stimulates GNM via increasing total N and MB, whereas higher precipitation stimulates GNM via increasing total N. Moreover, the GNM varies with ecosystem type, being greater in forests and grasslands with high total carbon and MB contents and low BD and pH compared to croplands. The highest GNM was observed in tropical wet soils that receive high precipitation, which increases the supply of soil substrate (total N) to microbes. Our findings suggest that anthropogenic activities that affect soil microbial population size, BD, soil substrate availability, or soil pH may interact with changes in precipitation regime and land use to influence GNM, which may ultimately affect ecosystem productivity and N loss to the environment.

Marinomonas vulgaris sp. nov., a marine bacterium isolated from seawater in a coastal intertidal zone of Zhoushan island - Jun-Jie Ying; Yuan-Chun Fang; Yong-Lian Ye; Zhi-Cheng Wu; Lin Xu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2021)

Geochemical characteristics of the lower Cambrian Qiongzhusi Formation in Huize area, east Yunnan: implications for paleo-ocean environment and the origin of black rock series - Yong Cheng; Weiqing Liu; Wei Wu; Yu Zhang; Guo Tang; Cong Liu; Qi Nie; Yiming Wen; Ping Lu; Chuanyu Zhang (Arabian Journal of Geosciences, 2021)

Aestuariibaculum sediminum sp. nov., a marine bacterium isolated from a tidal flat in Zhoushan - Zhi-Cheng Wu; Xin-Yin Zhang; Cong Sun; Lin Xu; Ge-Yi Fu; Xue-Wei Xu (Archives of Microbiology, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Heavy Metal Adsorption and Release on Polystyrene Particles at Various Salinities - Beta Susanto Barus; Kai Chen; Minggang Cai; Rongmao Li; Huorong Chen; Cong Li; Jun Wang; Sha-Yen Cheng (Frontiers in Marine Science, 2021)
Microplastics (MPs) and heavy metals are two major types of pollutants that interact with each other, but they are poorly understood. Polystyrene (PS) is one type of MPs that is often detected in aquatic environments. In this study, we examined the adsorption capacity and release rate of heavy metals with respect to different particle sizes of PS, heavy metals, initial heavy metal concentrations, and salinities. Virgin (new) PS with diameters of 20, 50, 130, and 250 μm was used in this study, and four heavy metals (lead, cadmium, copper, and zinc) were used. The results showed that larger PS particle sizes adsorbed more heavy metals even though it took longer to achieve equilibrium adsorption. An increase in heavy metal concentration caused the adsorption capacity (μg g –1 ) of PS particles to also increase, but the adsorption rate (%) decreased. Increased salinity of the heavy metal solution resulted in a slower adsorption time and a lower adsorption capacity and release rate from the surface of PS particles. Different heavy metals also had different adsorption capacities. Pb was consistently more highly adsorbed by MPs, followed by Cu, Zn, and Cd. Larger PS sizes released heavy metals faster than smaller PS sizes, and the amounts of heavy metals released were higher. The heavy metal with the highest release rate was Cd, followed by Pb, Cu, and Zn. Finally, our findings highlight the interactions between PS and heavy metals and strongly support that PS particles can act as vectors for heavy metals in aquatic systems.

Seismic active earth resistance of submerged backfill considering anisotropic seepage - Rui Huang; Nan Yang; Cong Cheng (Marine Georesources & Geotechnology, 2021)

Association between fine particulate matter and heart failure hospitalizations: a time-series analysis in Yancheng, China - Xu Li; Hongyi Cheng; Yan Fang; Zhichao Chen; Guangyu Qi; Renjie Chen; Haidong Kan; Cong Liu; Jingyan Cao (Environmental Science and Pollution Research, 2021)

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

Investigation on the dust migration behavior and safety zone in the fully mechanized mining face - Xin-xiao Lu; Cheng-yan Wang; Yun Xing; Cong Shen; Guo-yu Shi (Environmental Science and Pollution Research, 2021)

Altered white matter structural networks in drug-naïve patients with obsessive-compulsive disorder - Cong Zhou; Liangliang Ping; Wei Chen; Mengxin He; Jian Xu; Zonglin Shen; Yi Lu; Binli Shang; Xiufeng Xu; Yuqi Cheng (Brain Imaging and Behavior, 2021)

Experimental Research on Dynamic Evolution Characteristics of Roof Movement and Mining-Induced Stress of Superimposed Mining in a Close Distance Coal Seam Group - Zhiheng Cheng; Haifeng Ma; Cong Sang; Yanqing Liu (Geotechnical and Geological Engineering, 2021)

Genome-wide analysis of chloride channel-encoding gene family members and identification of CLC genes that respond to Cl−/salt stress in upland cotton - Xun Liu; Boyi Pi; Jianwei Pu; Cong Cheng; Jiajia Fang; Bingjun Yu (Molecular Biology Reports, 2020)

Evaluation of crustal inhomogeneity parameters in the southern Longmenshan fault zone and adjacent regions - Xiao-Ping Fan; Yi-Cheng He; Cong-Jie Yang; Jun-Fei Wang (Journal of Seismology, 2020)
Broadband teleseismic waveform data from 13 earthquakes recorded by 70 digital seismic stations were selected to evaluate the inhomogeneity parameters of the crustal medium in the southern Longmenshan fault zone and its adjacent regions using the teleseismic fluctuation wavefield method. Results show that a strong inhomogeneity exists beneath the study region, which can be divided into three blocks according to its structure and tectonic deformation features. These are known as the Sichuan-Qinghai Block, the Sichuan-Yunnan Block, and the Mid-Sichuan Block. The velocity fluctuation ratios of the three blocks are approximately 5.1%, 3.6%, and 5.1% in the upper crust and 5.1%, 3.8%, and 4.9% in the lower crust. The inhomogeneity correlation lengths of the three blocks are about 10.1 km, 14.0 km, and 10.7 km in the upper crust and 11.8 km, 17.0 km, and 11.8 km in the lower crust. The differences in the crustal medium inhomogeneity beneath the Sichuan-Yunnan Block, the Sichuan-Qinghai Block, and the Mid-Sichuan Block may be related to intensive tectonic movement and material flow in the crust and upper mantle.

RamA, a transcriptional regulator conferring florfenicol resistance in Leclercia adecarboxylata R25 - Cong Cheng; Yuanyuan Ying; Danying Zhou; Licheng Zhu; Junwan Lu; Aifang Li; Qiyu Bao; Mei Zhu (Folia Microbiologica, 2020)
Due to the inappropriate use of florfenicol in agricultural practice, florfenicol resistance has become increasingly serious. In this work, we studied the novel florfenicol resistance mechanism of an animal-derived Leclercia adecarboxylata strain R25 with high-level florfenicol resistance. A random genomic DNA library was constructed to screen the novel florfenicol resistance gene. Gene cloning, gene knockout, and complementation combined with the minimum inhibitory concentration (MIC) detection were conducted to determine the function of the resistance-related gene. Sequencing and bioinformatics methods were applied to analyze the structure of the resistance gene-related sequences. Finally, we obtained a regulatory gene of an RND (resistance-nodulation-cell division) system, ramA , that confers resistance to florfenicol and other antibiotics. The ramA -deleted variant (LA-R25Δ ramA ) decreased the level of resistance against florfenicol and several other antibiotics, while a ramA -complemented strain (pUCP24-prom- ramA/ LA-R25Δ ramA ) restored the drug resistance. The whole-genome sequencing revealed that there were five RND efflux pump genes ( mdtABC , acrAB , acrD , acrEF , and acrAB -like) encoded over the chromosome, and ramA located upstream of the acrAB -like genes. The results of this work suggest that ramA confers resistance to florfenicol and other structurally unrelated antibiotics, presumably by regulating the RND efflux pump genes in L. adecarboxylata R25.

Overexpression of PREX1 in oral squamous cell carcinoma indicates poor prognosis - Shu-Cheng Wan; Hao Wu; Hao Li; Wei-Wei Deng; Yao Xiao; Cong-Cong Wu; Lei-Lei Yang; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2020)

Fully multi-target segmentation for breast ultrasound image based on fully convolutional network - Yingtao Zhang; Yan Liu; Hengda Cheng; Ziyao Li; Cong Liu (Medical & Biological Engineering & Computing, 2020)

Optimising the measurement of peracetic acid to assess its degradation during drinking water disinfection - Kejia Zhang; Yulong San; Cong Cao; Tuqiao Zhang; Cheng Cen; Xinyan Zhou (Environmental Science and Pollution Research, 2020)

A special symptom of olfactory dysfunction in coronavirus disease 2019: report of three cases - Chen Chen; Moxian Chen; Cong Cheng; Yun Chi; Zhiliang Hu; Yuan Liu; Shan Huang; Yanling Lv; Chongfeng Liang; Damin Jiao; Yongxiang Yi; Xia Zhang; et al. (Journal of NeuroVirology, 2020)

Study on the Treatment of Nickel-Contaminated Soil Using Calcium Oxide - Zhen-li Xiang; Huan-fang Gao; Huan Yan; Ya-ling Li; Zhi-long Diao; En-zhi Zhang; Cong Li; Yuan-cheng Cao (Water, Air, & Soil Pollution, 2020)

Soil pH exerts stronger impacts than vegetation type and plant diversity on soil bacterial community composition in subtropical broad-leaved forests - Jingmin Cheng; Mengxin Zhao; Jing Cong; Qi Qi; Ye Xiao; Wei Cong; Ye Deng; Jizhong Zhou; Yuguang Zhang (Plant and Soil, 2020)

Appropriate Dynamically-Reinforced Supporting Time Determination in Relation to the Time Effect of Stress Field Evolution: A Case Study on the Deep Soft-Rock Roadway in China - Li Cong; Ying-ming Li; Xiang-rui Meng; Chun-liang Dong; Guang-ming Zhao; Rui Peng; Ji-cheng Xu (Geotechnical and Geological Engineering, 2020)

Clinical and biochemical indexes from 2019-nCoV infected patients linked to viral loads and lung injury - Yingxia Liu; Yang Yang; Cong Zhang; Fengming Huang; Fuxiang Wang; Jing Yuan; Zhaoqin Wang; Jinxiu Li; Jianming Li; Cheng Feng; Zheng Zhang; Lifei Wang; et al. (Science China Life Sciences, 2020)

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

Copper Changes Intestinal Microbiota of the Cecum and Rectum in Female Mice by 16S rRNA Gene Sequencing - Sufang Cheng; Huirong Mao; Yezhao Ruan; Cong Wu; Zheng Xu; Guoliang Hu; Xiaoquan Guo; Caiying Zhang; Huabin Cao; Ping Liu (Biological Trace Element Research, 2020)

Decellularization, cross-linking and heparin immobilization of porcine carotid arteries for tissue engineering vascular grafts - Zhiwen Cai; Yongquan Gu; Jin Cheng; Ji Li; Zeqin Xu; Yuehao Xing; Cong Wang; Zhonggao Wang (Cell and Tissue Banking, 2019)

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Foliar-applied lanthanum chloride increases growth and phosphorus acquisition in phosphorus-limited adzuki bean seedlings - Huida Lian; Cheng Qin; Cong Zhang; Minfei Yan; Hongbing Li; Suiqi Zhang (Plant and Soil, 2019)

Lanthanum nitrate improves phosphorus-use efficiency and tolerance to phosphorus-deficiency stress in Vigna angularis seedlings - Huida Lian; Cheng Qin; Li Zhang; Cong Zhang; Hongbing Li; Suiqi Zhang (Protoplasma, 2019)

Coal mine microseismic velocity model inversion based on first arrival time difference - Sen Cong; Yun-hong Wang; Jian-Yuan Cheng (Arabian Journal of Geosciences, 2019)

Novel nano-microspheres containing chitosan, hyaluronic acid, and chondroitin sulfate deliver growth and differentiation factor-5 plasmid for osteoarthritis gene therapy - Zhu Chen; Shang Deng; De-chao Yuan; Kang Liu; Xiao-cong Xiang; Liang Cheng; Dong-qin Xiao; Li Deng; Gang Feng (Journal of Zhejiang University-SCIENCE B, 2018)

MiR-92a inhibits fibroblast-like synoviocyte proliferation and migration in rheumatoid arthritis by targeting AKT2 - Fang-Yuan Yu; Cong-Qin Xie; Chang-liang Jiang; Ji-Tong Sun; Hui-Cheng Feng; Chao Li; Xun-Wu Huang (Journal of Biosciences, 2018)

Water Resources and Farmland Management in the Songhua River Watershed under Interval and Fuzzy Uncertainties - Cong Dong; Gordon Huang; Guanhui Cheng; Shan Zhao (Water Resources Management, 2018)

Climatic role of terrestrial ecosystem under elevated CO 2 : a bottom‐up greenhouse gases budget - Shuwei Liu; Cheng Ji; Cong Wang; Jie Chen; Yaguo Jin; Ziheng Zou; Shuqing Li; Shuli Niu; Jianwen Zou (Ecology Letters, 2018)
The net balance of greenhouse gas ( GHG ) exchanges between terrestrial ecosystems and the atmosphere under elevated atmospheric carbon dioxide ( CO 2 ) remains poorly understood. Here, we synthesise 1655 measurements from 169 published studies to assess GHG s budget of terrestrial ecosystems under elevated CO 2 . We show that elevated CO 2 significantly stimulates plant C pool ( NPP ) by 20%, soil CO 2 fluxes by 24%, and methane ( CH 4 ) fluxes by 34% from rice paddies and by 12% from natural wetlands, while it slightly decreases CH 4 uptake of upland soils by 3.8%. Elevated CO 2 causes insignificant increases in soil nitrous oxide (N 2 O) fluxes (4.6%), soil organic C (4.3%) and N (3.6%) pools. The elevated CO 2 ‐induced increase in GHG emissions may decline with CO 2 enrichment levels. An elevated CO 2 ‐induced rise in soil CH 4 and N 2 O emissions (2.76 Pg CO 2 ‐equivalent year −1 ) could negate soil C enrichment (2.42 Pg CO 2 year −1 ) or reduce mitigation potential of terrestrial net ecosystem production by as much as 69% ( NEP , 3.99 Pg CO 2 year −1 ) under elevated CO 2 . Our analysis highlights that the capacity of terrestrial ecosystems to act as a sink to slow climate warming under elevated CO 2 might have been largely offset by its induced increases in soil GHG s source strength.

A guanine insert in OsBBS1 leads to early leaf senescence and salt stress sensitivity in rice (Oryza sativa L.) - Dong-Dong Zeng; Cheng-Cong Yang; Ran Qin; Md. Alamin; Er-Kui Yue; Xiao-Li Jin; Chun-Hai Shi (Plant Cell Reports, 2018)

Seismic responses of the steel-strip reinforced soil retaining wall with full-height rigid facing from shaking table test - Li-cong Cao; Xiao Fu; Zhi-jia Wang; Yong-yi Zhou; Fei-cheng Liu; Jian-jing Zhang (Journal of Mountain Science, 2018)

Complete nucleotide sequence of jasmine virus H, a new member of the family Tombusviridae - Tao Zhuo; Li-Juan Zhu; Cheng-Cong Lu; Chao-Yang Jiang; Zi-Yin Chen; Guangzhi Zhang; Zong-Hua Wang; Juan Jovel; Yan-Hong Han (Archives of Virology, 2018)

Resources and environmental systems management under synchronic interval uncertainties - Guanhui Cheng; Guohe Huang; Cong Dong; Ying Lv; Junlong Zhang; Yao Yao; Xiujuan Chen (Stochastic Environmental Research and Risk Assessment, 2018)

Midazolam prevents motor neuronal death from oxidative stress attack mediated by JNK-ERK pathway - Guo-zheng Li; Hong-Lei Tao; Cheng Zhou; Dong-dong Wang; Cong-bin Peng (Human Cell, 2018)

Numerical modeling and dynamic analysis of the 2017 Xinmo landslide in Maoxian County, China - Chao-jun Ouyang; Wei Zhao; Si-ming He; Dong-po Wang; Shu Zhou; Hui-cong An; Zhong-wen Wang; Duo-xiang Cheng (Journal of Mountain Science, 2017)

Climate classification through recursive multivariate statistical inferences: a case study of the Athabasca River Basin, Canada - Guanhui Cheng; Guohe Huang; Cong Dong; Xiong Zhou; Jinxin Zhu; Ye Xu (International Journal of Climatology, 2017)
In this study, a recursive dissimilarity and similarity inferential climate classification ( ReDSICC ) approach is developed to provide an alternative tool for climate classification. Based on incorporation of a discrete distribution transformation ( DDT ) method and integration of advanced statistical inferential methods, a recursive framework of dissimilarity and similarity inferences is proposed for stepwise grouping multi‐dimensional climate‐variable observations. ReDSICC is capable of eliminating the restriction of samples being normally distributed, enabling classification of regional climates under data uncertainties and multivariate dependencies, identifying the most desired climate classification result, and avoiding subjective judgments in the classification process. To verify methodological effectiveness and facilitate related studies, ReDSICC is applied to climate classification in the Athabasca River Basin ( ARB ), Canada. It is revealed that the complicated dissimilarities and similarities of climatic conditions among all grids over the ARB are effectively reflected in the results of ReDSICC . A reversible transformation between an abnormal distribution and a normal distribution is achieved by DDT . The effectiveness of climate classification which is represented as the Nash coefficient for climatic features over any grid and the corresponding climate class is decreased if DDT is not employed. In comparison with daily minimum temperature, the spatial heterogeneity of daily maximum temperature is higher while that of daily cumulative precipitation is lower over the ARB . The classification result of ReDSICC varies with changes of representative climate variables and parameter values. These advantages and revelations are helpful for enhancing the reliability of climate classification results, improving the effectiveness of existing climate classification methods, and providing scientific support for the related studies in the ARB or neighbouring regions.

Hydraulic Analysis of Water Distribution Systems Based on Fixed Point Iteration Method - Hui Zhang; Xin Cheng; Tinglin Huang; Haibing Cong; Jinlan Xu (Water Resources Management, 2017)

Distributed mixed-integer fuzzy hierarchical programming for municipal solid waste management. Part II: scheme analysis and mechanism revelation. - Guanhui Cheng; Guohe Huang; Cong Dong; Ye Xu; Jiapei Chen; Xiujuan Chen; Kailong Li (Environmental Science and Pollution Research, 2017)

Distributed mixed-integer fuzzy hierarchical programming for municipal solid waste management. Part I: System identification and methodology development - Guanhui Cheng; Guohe Huang; Cong Dong; Ye Xu; Xiujuan Chen; Jiapei Chen (Environmental Science and Pollution Research, 2017)

Convex contractive interval linear programming for resources and environmental systems management - Guanhui Cheng; Guohe Huang; Cong Dong (Stochastic Environmental Research and Risk Assessment, 2017)

Tumor Targeting Synergistic Drug Delivery by Self-Assembled Hybrid Nanovesicles to Overcome Drug Resistance - Meng-Qing Gong; Cong Wu; Xiao-Yan He; Jing-Yi Zong; Jin-Long Wu; Ren-Xi Zhuo; Si-Xue Cheng (Pharmaceutical Research, 2017)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

DBOP specifies palea development by suppressing the expansion of the margin of palea in rice - Dong-Dong Zeng; Ran Qin; Md. Alamin; Rong Liang; Cheng-Cong Yang; Xiao-Li Jin; Chun-Hai Shi (Genes & Genomics, 2016)

Light carbon isotope events of foraminifera attributed to methane release from gas hydrates on the continental slope, northeastern South China Sea - Chang Zhuang; Fang Chen; SiHai Cheng; HongFeng Lu; Cong Wu; Jun Cao; Xiao Duan (Science China Earth Sciences, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Retrieval of sea surface winds under hurricane conditions from GNSS-R observations - Cheng Jing; Xiaofeng Yang; Wentao Ma; Yang Yu; Di Dong; Ziwei Li; Cong Xu (Acta Oceanologica Sinica, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Rhodiola rosea extends lifespan and improves stress tolerance in silkworm, Bombyx mori - Cong Chen; Jiangbo Song; Min Chen; Zhiquan Li; Xiaoling Tong; Hai Hu; Zhonghuai Xiang; Cheng Lu; Fangyin Dai (Biogerontology, 2016)

Dual-reporter Imaging and its Potential Application in Tracking Studies - Jie Ding; Chao Wang; Pei-Cheng Li; Zhen Zhao; Cheng Qian; Cong-Xiao Wang; Yu Cai; Gao-Jun Teng (Journal of Fluorescence, 2016)

Prevalence of Balantidium coli infection in sows in Hunan province, subtropical China - De-Ming Yin; Cong-Cong Lv; Lei Tan; Tie-Niu Zhang; Cheng-Zhi Yang; Yi Liu; Wei Liu (Tropical Animal Health and Production, 2015)

Saccharothrix lopnurensis sp. nov., a filamentous actinomycete isolated from sediment of Lop Nur - Yu-Qian Li; Lan Liu; Cong Cheng; Xiao-Han Shi; Chun-Yan Lu; Zhou-Yan Dong; Nimaichand Salam; Deng-Di An; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Genome-wide identification and characterization of Fox genes in the silkworm, Bombyx mori - JiangBo Song; ZhiQuan Li; XiaoLing Tong; Cong Chen; Min Chen; Gang Meng; Peng Chen; ChunLin Li; YaQun Xin; TingTing Gai; FangYin Dai; Cheng Lu (Functional & Integrative Genomics, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Tobacco rattle virus mediated gene silencing in strawberry plants - Ji Tian; Li Cheng; Zhen-yun Han; Yun-cong Yao (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

3D-QSAR and docking study on 3-benzimidazol-2-ylhydroquinolin-2-one derivatives as VEGFR-2 tyrosine kinase inhibitors - Cong-min Kang; Dong-qing Liu; Xin-yu Wang; Ying-jie Dai; Jia-gao Cheng; Ying-tao Lv (Medicinal Chemistry Research, 2015)

Enhanced photo-H2 production by unsaturated flow condition in continuous culture - Cheng-Long Guo; Hong-Xia Cao; Fei-Qiang Guo; Cong-Liang Huang; Huan-Guang Wang; Zhong-Hao Rao (Biotechnology Letters, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Expression and localization of transcription factors SNAIL and SLUG in mouse ovaries and pre-implantation embryos - Cui Guo; Xiaoqian Meng; Jing Bai; Cheng Chen; Tao Liu; Shuzhen Liu; Cong Zhang; Wei-Ping Li (Cell and Tissue Research, 2014)

Screening and monitoring zearalenone-producing Fusarium species by PCR and zearalenone by monoclonal antibodies in feed from China - Shi-Chun Pei; Yu-Ping Zhen; Jian-Wei Gao; Won-Jong Lee; Hong-Fu Zhang; Cheng Ji; Xuan-Zhe Zhang; Cong Chen (Food Additives & Contaminants Part B-Surveillance, 2014)

Landslide stability analysis based on random-fuzzy reliability: taking Liangshuijing landslide as a case - Wu Yiping; Cheng Cong; He Gaofeng; Zhang Qiuxia (Stochastic Environmental Research and Risk Assessment, 2014)

Effects of soil moisture on gross N transformations and N2O emission in acid subtropical forest soils - Yi Cheng; Jing Wang; Shen-Qiang Wang; Jin-Bo Zhang; Zu-Cong Cai (Biology and Fertility of Soils, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Comparative proteome analysis of the response of ramie under N, P and K deficiency - Gang Deng; Li Jun Liu; Xin Yue Zhong; Cheng Ying Lao; Hong Yang Wang; Bo Wang; Cong Zhu; Fahad Shah; Ding Xiang Peng (Planta, 2014)

Effect of miR-205 on 3T3-L1 preadipocyte differentiation through targeting to glycogen synthase kinase 3 beta - Jingwei Yu; Yaosheng Chen; Limei Qin; Luxi Cheng; Guangcai Ren; Peiqing Cong; Delin Mo; Zuyong He (Biotechnology Letters, 2014)

The mechanisms behind reduced NH4 + and NO3 − accumulation due to litter decomposition in the acidic soil of subtropical forest - Yi Cheng; Jing Wang; Jin-Bo Zhang; Bruno Mary; Zu-Cong Cai (Plant and Soil, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

Litter decomposition reduces either N2O or NO production in strongly acidic coniferous and broad-leaved forest soils under anaerobic conditions - Yi Cheng; Jing Wang; Yang Liu; Zu-Cong Cai (Journal of Soils and Sediments, 2014)

Depressed calcium-handling proteins due to endoplasmic reticulum stress and apoptosis in the diabetic heart are attenuated by argirein - F. H. Shi; Y. S. Cheng; D. Z. Dai; H. J. Peng; X. D. Cong; Y. Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Circulating IL-21 levels increase during early simian-human immunodeficiency virus infection in macaques - Chang-cheng Zhao; Jing Xue; Zhe Cong; Xi-qiang Gao; Wei-lun Zhang; Ting Chen; Fang-xin Wu; Jing Xiong; Bin Ju; Aihua Su; Qiang Wei; Chuan Qin (Archives of Virology, 2013)

Role of autophagy in early brain injury after subarachnoid hemorrhage in rats - Hongbo Zhao; Zhiyong Ji; Deji Tang; Cong Yan; Wenyang Zhao; Cheng Gao (Molecular Biology Reports, 2013)

Wheat straw and its biochar have contrasting effects on inorganic N retention and N2O production in a cultivated Black Chernozem - Yi Cheng; Zu-cong Cai; Scott X. Chang; Jing Wang; Jin-bo Zhang (Biology and Fertility of Soils, 2012)

Genome sequence determination and analysis of a Chinese virulent strain, LMS, of Gallid herpesvirus type 2 - Yun Cheng; Feng Cong; Yan-ping Zhang; Zhi-jie Li; Na-na Xu; Guang-yu Hou; Chang-jun Liu (Virus Genes, 2012)

Soil moisture effects on gross nitrification differ between adjacent grassland and forested soils in central Alberta, Canada - Yi Cheng; Zu-cong Cai; Jin-bo Zhang; Man Lang; Bruno Mary; Scott X. Chang (Plant and Soil, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

Differential expression of oncogenic miRNAs in proliferating and senescent human fibroblasts - Miao Wang; Zhaojie Cheng; Tian Tian; Jingwen Chen; Fei Dou; Mingzhou Guo; Yu-Sheng Cong (Molecular and Cellular Biochemistry, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Comparative temporal analyses of the Pinus sylvestris L. var. mongolica litv. apical bud proteome from dormancy to growth - Ying-Dong Bi; Zhi-Gang Wei; Zhuo Shen; Tian-Cong Lu; Yu-Xiang Cheng; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2011)

cDNA cloning and expression analysis of wheat (Triticum aestivum L.) phytoene and ζ-carotene desaturase genes - Ling Cong; Cheng Wang; Zhiqiang Li; Ling Chen; Guangxiao Yang; Yuesheng Wang; Guangyuan He (Molecular Biology Reports, 2010)

Porphyrin and Galactosyl Conjugated Micelles for Targeting Photodynamic Therapy - De-Qun Wu; Ze-Yong Li; Cao Li; Jian-Jun Fan; Bo Lu; Cong Chang; Si-Xue Cheng; Xian-Zheng Zhang; Ren-Xi Zhuo (Pharmaceutical Research, 2010)

Identification and Experimental Verification of Protective Antigens Against Streptococcus suis Serotype 2 Based on Genome Sequence Analysis - Lina Liu; Gong Cheng; Changjun Wang; Xiuzhen Pan; Yanguang Cong; Qu Pan; Jing Wang; Feng Zheng; Fuquan Hu; Jiaqi Tang (Current Microbiology, 2009)

Expression of β-carotene hydroxylase gene (crtR-B) from the green alga Haematococcus pluvialis in chloroplasts of Chlamydomonas reinhardtii - Cong-Ping Tan; Fang-Qing Zhao; Zhong-Liang Su; Cheng-Wei Liang; Song Qin (Journal of Applied Phycology, 2007)

Agrobacterium-mediated transformation of the apple rootstock Malus micromalus Makino with the RolC gene - Zhen Zhang; Aijun Sun; Yu Cong; Bingcheng Sheng; Quanhong Yao; Zong-Ming Cheng (In Vitro Cellular & Developmental Biology - Plant, 2006)

Molecular Cloning, Characterization and Evolutionary Analysis of Phytoene Desaturase (PDS) Gene from Haematococcus pluvialis - Cheng W. Liang; Fang Q. Zhao; Chun X. Meng; Cong P. Tan; Song Qin (World Journal of Microbiology and Biotechnology, 2006)

Dechlorination by combined electrochemical reduction and oxidation - Yan-qing Cong; Zu-cheng Wu; Tian-en Tan (Journal of Zhejiang University-SCIENCE B, 2005)